Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2023)
A dataset containing 478259035 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is one of (Acomys minous Bate, 1906, Acomys nesiotes Bate, 1903, Alces alces (Linnaeus, 1758), Alexandromys middendorffii (Poljakov, 1881), Alexandromys oeconomus (Pallas, 1776), Allactaga major (Kerr, 1792), Allocricetulus eversmanni (Brandt, 1859), Apodemus agrarius (Pallas, 1771), Apodemus alpicola Heinrich, 1952, Apodemus epimelas (Nehring, 1902), Apodemus flavicollis (Melchior, 1834), Apodemus mystacinus (Danford & Alston, 1877), Apodemus ponticus (Sviridenko, 1936), Apodemus sylvaticus (Linnaeus, 1758), Apodemus uralensis (Pallas, 1811), Apodemus witherbyi (Thomas, 1902), Arvicola scherman (Shaw, 1801), Atelerix algirus (Lereboullet, 1842), Atlantoxerus getulus (Linnaeus, 1758), Barbastella barbastellus (Schreber, 1774), Barbastella leucomelas (Cretzschmar, 1826), Bison bonasus (Linnaeus, 1758), Canis aureus Linnaeus, 1758, Canis lupaster Hemprich & Ehrenberg, 1833, Canis lupus Linnaeus, 1758, Capra aegagrus Erxleben, 1777, Capra caucasica Güldenstaedt & Pallas, 1783, Capra cylindricornis (Blyth, 1841), Capra ibex Linnaeus, 1758, Capra pyrenaica Schinz, 1838, Capreolus capreolus (Linnaeus, 1758), Capreolus pygargus (Pallas, 1771), Caracal caracal (Schreber, 1776), Cervus elaphus Linnaeus, 1758, Chionomys gud (Satunin, 1909), Chionomys roberti (Thomas, 1906), Chionomys Miller, 1908, Clethrionomys glareolus (Schreber, 1780), Clethrionomys rutilus (Pallas, 1779), Craseomys rufocanus (Sundevall, 1846), Cricetus cricetus (Linnaeus, 1758), Crocidura canariensis Hutterer, Lopez-Jurado & Vogel, 1987, Crocidura leucodon (Hermann, 1780), Crocidura pachyura (Kuster, 1835), Crocidura russula (Hermann, 1780), Crocidura sicula Miller, 1900, Crocidura suaveolens (Pallas, 1811), Crocidura whitakeri de Winton, 1898, Crocidura zimmermanni Wettstein, 1953, Dama dama (Linnaeus, 1758), Dicrostonyx torquatus (Pallas, 1778), Dinaromys bogdanovi (Martino, 1922), Diplomesodon pulchellum (Lichtenstein, 1823), Dipus sagitta (Pallas, 1773), Dryomys nitedula (Pallas, 1778), Eliomys munbyanus (Pomel, 1856), Eliomys quercinus (Linnaeus, 1766), Ellobius talpinus (Pallas, 1770), Eptesicus anatolicus Felten, 1971, Eptesicus bobrinskoi Kuzyakin, 1935, Eptesicus isabellinus (Temminck, 1840), Eptesicus nilssonii (Keyserling & Blasius, 1839), Eptesicus ognevi Bobrinskii, 1918, Eptesicus serotinus (Schreber, 1774), Erinaceus concolor Martin, 1838, Erinaceus europaeus Linnaeus, 1758, Erinaceus roumanicus Barrett-Hamilton, 1900, Eutamias sibiricus (Laxmann, 1769), Felis chaus Schreber, 1777, Felis lybica Forster, 1780, Felis silvestris Schreber, 1777, Gazella dorcas (Linnaeus, 1758), Genetta genetta (Linnaeus, 1758), Gerbillus campestris (Loche, 1867), Glis glis (Linnaeus, 1766), Gulo gulo (Linnaeus, 1758), Hemiechinus auritus (Gmelin, 1770), Herpestes ichneumon (Linnaeus, 1758), Hyaena hyaena (Linnaeus, 1758), Hypsugo savii (Bonaparte, 1837), Hystrix cristata Linnaeus, 1758, Ictonyx libycus (Hemprich & Ehrenberg, 1833), Jaculus orientalis Erxleben, 1777, Lagurus lagurus (Pallas, 1773), Lasiopodomys gregalis Pallas, 1779, Lemmus sibiricus (Kerr, 1792), Lemniscomys barbarus (Linnaeus, 1767), Lepus capensis Linnaeus, 1758, Lepus castroviejoi Palacios, 1977, Lepus corsicanus de Winton, 1898, Lepus europaeus Pallas, 1778, Lepus granatensis Rosenhauer, 1856, Lepus timidus Linnaeus, 1758, Lepus tolai Pallas, 1778, Lynx lynx (Linnaeus, 1758), Lynx pardinus (Temminck, 1827), Macaca sylvanus (Linnaeus, 1758), Marmota bobak (Müller, 1776), Marmota marmota (Linnaeus, 1758), Martes foina (Erxleben, 1777), Martes martes (Linnaeus, 1758), Martes zibellina (Linnaeus, 1758), Meles leucurus (Hodgson, 1847), Meles meles (Linnaeus, 1758), Meriones grandis Cabrera, 1907, Meriones meridianus (Pallas, 1773), Meriones tamariscinus (Pallas, 1773), Meriones tristrami Thomas, 1892, Mesocricetus brandti (Nehring, 1898), Mesocricetus newtoni (Nehring, 1898), Mesocricetus raddei (Nehring, 1894), Micromys minutus (Pallas, 1771), Microtus agrestis (Linnaeus, 1761), Microtus arvalis (Pallas, 1779), Microtus bavaricus Konig, 1962, Microtus brachycercus Lehmann, 1961, Microtus cabrerae Thomas, 1906, Microtus daghestanicus (Shidlovsky, 1919), Microtus duodecimcostatus (Selys-Longchamps, 1839), Microtus felteni Malec & Storch, 1963, Microtus gerbei (Gerbe, 1879), Microtus guentheri (Danford & Alston, 1880), Microtus liechtensteini (Wettstein, 1927), Microtus lusitanicus (Gerbe, 1879), Microtus majori Thomas, 1906, Microtus multiplex (Fatio, 1905), Microtus mystacinus (De Filippi, 1865), Microtus savii (Selys-Longchamps, 1838), Microtus socialis (Pallas, 1773), Microtus subterraneus (Selys-Longchamps, 1836), Microtus tatricus Kratochvíl, 1952, Microtus thomasi (Barrett-Hamilton, 1903), Miniopterus pallidus Thomas, 1907, Miniopterus schreibersii (Kuhl, 1817), Muntiacus reevesi (Ogilby, 1839), Mus cypriacus Cucchi, Orth, Auffray, Renaud, Fabre, Catalan, Hadjisterkotis, Bonhomme & Vigne, 2006, Mus macedonicus Petrov & Ruzic, 1983, Mus musculus Linnaeus, 1758, Mus spicilegus Petényi, 1882, Mus spretus Lataste, 1883, Muscardinus avellanarius (Linnaeus, 1758), Mustela erminea Linnaeus, 1758, Mustela eversmanii Lesson, 1827, Mustela nivalis Linnaeus, 1766, Mustela putorius Linnaeus, 1758, Mustela sibirica Pallas, 1773, Myomimus roachi (Bate, 1937), Myopus schisticolor (Lilljeborg, 1844), Myotis alcathoe von Helversen & Heller, 2001, Myotis aurascens Kuzyakin, 1935, Myotis bechsteinii (Kuhl, 1817), Myotis blythii (Tomes, 1857), Myotis brandtii (Eversmann, 1845), Myotis capaccinii (Bonaparte, 1837), Myotis dasycneme (Boie, 1825), Myotis daubentonii (Kuhl, 1817), Myotis emarginatus (E.Geoffroy, 1806), Myotis escalerai Cabrera, 1904, Myotis myotis (Borkhausen, 1797), Myotis mystacinus (Kuhl, 1817), Myotis nattereri (Kuhl, 1817), Myotis punicus Felten, Spitzenberger & Storch, 1977, Nannospalax leucodon (Nordmann, 1840), Nannospalax xanthodon (Nordman, 1840), Nothocricetulus Lebedev, Bannikova, Neumann, Ushakova, Ivanova & Surov, 2018, Nyctalus azoreum (Thomas, 1901), Nyctalus lasiopterus (Schreber, 1780), Nyctalus leisleri (Kuhl, 1817), Nyctalus noctula (Schreber, 1774), Nyctereutes procyonoides (Gray, 1834), Ochotona hyperborea (Pallas, 1811), Ochotona pusilla (Pallas, 1769), Oryctolagus cuniculus (Linnaeus, 1758), Ovibos moschatus (Zimmermann, 1780), Ovis gmelini Linnaeus, 1758, Pachyuromys duprasi Lataste, 1880, Panthera pardus (Linnaeus, 1758), Pipistrellus hanaki Hulva & Benda, 2004, Pipistrellus kuhlii (Kuhl, 1817), Pipistrellus maderensis (Dobson, 1878), Pipistrellus nathusii (Keyserling & Blasius, 1839), Pipistrellus pipistrellus (Schreber, 1774), Pipistrellus pygmaeus (Leach, 1825), Plecotus auritus (Linnaeus, 1758), Plecotus austriacus (J.Fischer, 1829), Plecotus kolombatovici Dulic, 1980, Plecotus macrobullaris Kuzyakin, 1965, Plecotus sardus Mucedda, Kiefer, Pidinchedda & Veith, 2002, Plecotus teneriffae Barrett-Hamilton, 1907, Prometheomys schaposchnikowi Satunin, 1901, Pteromys volans (Linnaeus, 1758), Pygeretmus pumilio (Kerr, 1792), Rangifer tarandus (Linnaeus, 1758), Rattus norvegicus (Berkenhout, 1769), Rattus rattus (Linnaeus, 1758), Rhinolophus blasii Peters, 1867, Rhinolophus euryale Blasius, 1853, Rhinolophus ferrumequinum (Schreber, 1774), Rhinolophus hipposideros (Bechstein, 1800), Rhinolophus mehelyi Matschie, 1901, Rousettus aegyptiacus (E.Geoffroy, 1810), Rupicapra pyrenaica Bonaparte, 1845, Rupicapra rupicapra (Linnaeus, 1758), Saiga tatarica (Linnaeus, 1766), Scarturus elater (H.Lichtenstein, 1825), Scarturus williamsi Thomas, 1897, Sciurus anomalus Gmelin, 1778, Sciurus vulgaris Linnaeus, 1758, Sicista betulina (Pallas, 1779), Sicista caucasica Vinogradov, 1925, Sicista kazbegica Sokolov, Baskevich & Kovalskaya, 1986, Sicista kluchorica Sokolov, Kovalskaya & Baskevich, 1980, Sicista loriger (Nathusius, 1840), Sicista severtzovi Ognev, 1935, Sicista strandi Formozov, 1931, Sicista subtilis (Pallas, 1773), Sicista trizona (Frivaldszky, 1865), Sorex alpinus Schinz, 1837, Sorex antinorii Bonaparte, 1840, Sorex araneus Linnaeus, 1758, Sorex caecutiens Laxmann, 1788, Sorex coronatus Millet, 1828, Sorex daphaenodon Thomas, 1907, Sorex granarius Miller, 1910, Sorex isodon Turov, 1924, Sorex minutissimus Zimmermann, 1780, Sorex minutus Linnaeus, 1766, Sorex raddei Satunin, 1895, Sorex samniticus Altobello, 1926, Sorex satunini Ognev, 1922, Sorex tundrensis Merriam, 1900, Sorex volnuchini Ognev, 1922, Spalax antiquus Méhely, 1909, Spalax arenarius Reshetnik, 1939, Spalax giganteus Nehring, 1898, Spalax graecus Nehring, 1898, Spalax microphthalmus Guldenstaedt, 1770, Spalax zemni (Erxleben, 1777), Spermophilus citellus (Linnaeus, 1766), Spermophilus fulvus (Lichtenstein, 1823), Spermophilus major (Pallas, 1778), Spermophilus musicus Ménétries, 1832, Spermophilus pygmaeus (Pallas, 1778), Spermophilus suslicus (Güldenstaedt, 1770), Stylodipus telum (Lichtenstein, 1823), Suncus etruscus (Savi, 1822), Sus scrofa Linnaeus, 1758, Tadarida teniotis (Rafinesque, 1814), Talpa caeca Savi, 1822, Talpa caucasica Satunin, 1908, Talpa europaea Linnaeus, 1758, Talpa levantis Thomas, 1906, Talpa occidentalis Cabrera, 1907, Talpa romana Thomas, 1902, Talpa stankovici V.Martino & E.Martino, 1931, Ursus arctos Linnaeus, 1758, Vespertilio murinus Linnaeus, 1758, Vormela peregusna (Güldenstädt, 1770), Vulpes corsac (Linnaeus, 1768), Vulpes vulpes (Linnaeus, 1758), Arvicola middendorffi Poliakov, 1881, Microtus oeconomus (Pallas, 1776), Allactaga jaculus (Pallas, 1779), Apodemus arianus (Blanford, 1881), Apodemus fulvipectus (Ognev, 1924), Erinaceus algirus Lereboullet, 1842, Barbastella blandfordi Bianchi, 1917, Bos bonasus Linnaeus, 1758, Canis anthus F.Cuvier, 1820, Cervus capreolus Linnaeus, 1758, Capreolus bedfordi Thomas, 1908, Felis caracal Schreber, 1776, Chionomys nivalis (Martins, 1842), Chionomys personatus Ognev, 1924, Myodes glareolus (Schreber, 1780), Mus rutilus Pallas, 1779, Clethrionomys rufocanus (Sundevall, 1846), Crocidura cossyrensis Contoli, 1989, Crocidura osorio Molina & Hutterer, 1989, Crocidura gueldenstaedtii (Pallas, 1811), Diplomesodon pulchellum (Lichtenstein, 1823), Dryomys Thomas, 1906, Eptesicus japonensis Imaizumi, 1953, Eptesicus lobatus Zagorodniuk, 2009, Tamias sibiricus (Laxmann, 1769), Viverra genetta Linnaeus, 1758, Dipodillus campestris (Levaillant, 1857), Myoxus glis (Linnaeus, 1766), Gulo luscus Linnaeus, 1758, Viverra ichneumon Linnaeus, 1758, Canis hyaena Linnaeus, 1758, Pipistrellus savii (Bonaparte, 1837), Ictonyx libyca (Hemprich & Ehrenberg, 1833), Microtus gregalis (Pallas, 1779), Arvicanthis barbarus (Linnaeus, 1766), Macaca sylvanus (Linnaeus, 1758), Mus marmota Linnaeus, 1758, Mustela foina Erxleben, 1777, Meles canescens Blanford, 1875, Mesocricetus koenigi Nehring, 1900, Cricetus newtoni Nehring, 1898, Cricetus nigricans Brandt, 1832, Mus agrestis Linnaeus, 1761, Pitymys bavaricus Konig, 1962, Arvicola gerbii Gerbe, 1879, Arvicola guentheri (Danford & Alston, 1880), Pitymys liechtensteini Wettstein, 1927, Arvicola mystacinus de Filippi, 1865, Arvicola savii de Selys-Longchamps, 1838, Cervulus bridgemani Lydekker, 1910, Mus abbotti Waterhouse, 1837, Mus avellanarius Linnaeus, 1758, Mustela amurensis (Ognev, 1930), Myomimus bulgaricus Rossolimo, 1976, Myotis hajastanicus Argyropulo, 1939, Myotis bechsteini (Kuhl, 1817), Myotis oxygnathus (Monticelli, 1885), Vespertilio emarginatus E.Geoffroy, 1806, Myotis escalerae Cabrera, 1904, Spalax leucodon Nordmann, 1840, Nannospalax nehringi (Satunin, 1898), Cricetulus migratorius (Pallas, 1773), Pterygistes azoreum Thomas, 1901, Canis procyonoides Gray, 1834, Bos moschatus E.A.W.Zimmermann, 1780, Ovis orientalis Gmelin, 1774, Felis pardus Linnaeus, 1758, Pipistrellus deserti Thomas, 1902, Vespertilio pipistrellus Schreber, 1774, Plecotus alpinus Kiefer & Veith, 2002, Sciurus volans Linnaeus, 1758, Cervus tarandus Linnaeus, 1758, Mus norvegicus Berkenhout, 1769, Pteropus aegyptiacus E.Geoffroy, 1810, Capra tatarica Linnaeus, 1766, Allactaga elater (Lichtenstein, 1828), Allactaga williamsi Thomas, 1897, Sicista nordmanni Keyserling & Blasius, 1840, Sorex arunchi Lapini & Testone, 1998, Sorex averini Zubko, 1937, Sorex sanguinidens G.Allen, 1914, Sorex caucasicus Satunin, 1915, Sorex caucasicus Satunin, 1915, Spalax podolicus Trouessart, 1897, Citellus fulvus Lichtenstein, 1823, Citellus major Pallas, 1779, Citellus pygmaeus Pallas, 1778, Sorex etruscus Savi, 1822, Sus andamanensis Blyth, 1858, Talpa caeca Savi, 1822, Mustela peregusna Güldenstädt, 1770, Canis vulpes Linnaeus, 1758, Cervus alces Linnaeus, 1758, Microtus middendorffi (Poliakov, 1881), Mus oeconomus Pallas, 1776, Apodemus hermonensis Filippucci, Simson & Nevo, 1989, Barbastella caspica Satunin, 1908, Microtus nivalis (Martins, 1842), Microtus pshavus Shidlovsky, 1919, Hypudaeus syriacus Brants, 1827, Myodes rutilus (Pallas, 1779), Clethrionomys sikotanensis (Tokuda, 1935), Crocidura ichnusae Festa, 1912, Sorex suaveolens Pallas, 1811, Sorex pulchellum Lichtenstein, 1823, Eptesicus nilssoni (Keyserling & Blasius, 1839), Gerbillus quadrimaculatus Lataste, 1882, Mustela gulo Linnaeus, 1758, Mus barbarus Linnaeus, 1766, Simia sylvanus Linnaeus, 1758, Ursus meles Linnaeus, 1758, Mesocricetus nigriculus Nehring, 1898, Microtus obscurus (Eversmann, 1841), Microtus gerbei (Gerbe, 1879), Microtus mustersi Hinton, 1926, Microtus epiroticus Ondrias, 1966, Cervulus micrurus Sclater, 1875, Mus domesticus Rutty, 1772, Mustela eversmannii Lesson, 1827, Philistomys roachi Bate, 1937, Spalax munzuri Coşkun, 2004, Mus migratorius Pallas, 1773, Vespertilio kuhlii Kuhl, 1817, Vesperugo pipistrellus (Schreber, 1774), Plecotus microdontus Spitzenberger, 2002, Rattus caraco Pallas, 1779, Rousettus egyptiacus (E.Geoffroy, 1810), Ibex imberbis Gmelin, 1760, Dipus elater H.Lichtenstein, 1825, Sorex scaloni Ognev, 1933, Spalax polonicus Méhely, 1909, Suncus madagascariensis (Coquerel, 1848), Sus aruensis Rosenberg, 1878, Microtus middendorffii (Poliakov, 1881), Barbastella walteri Bianchi, 1916, Capreolus melanotis Miller, 1911, Microtus Schrank, 1798, Hypudaeus rufocanus Sundevall, 1846, Dryomys Thomas, 1906, Mus gregalis Pallas, 1779, Microtus pyrenaicus (de Sélys-Longchamps, 1839), Microtus levis Miller, 1908, Animalia, Myotis Kaup, 1829, Spalax nehringi (Satunin, 1898), Rattus caspius Oken, 1816, Sminthus loriger Nathusius, 1840, Sus babi Miller, 1906, Plecotus darjelingensis Hodgson, 1855, Myodes rufocanus (Sundevall, 1846), Mus nitedula Pallas, 1778, Microtus rossiaemeridionalis Ognev, 1924, Cervulus sclateri Swinhoe, 1872, Spalax xanthodon Nordman, 1840, Rattus decimallus Pallas, 1779, Sus ceramensis Rosenberg, 1878, Vespertilio leucomelas Cretzschmar, 1826, Capreolus tianschanicus Saturnin, 1906, Myoxus pictus Blanford, 1875, Microtus subarvalis Meyer, Orlov & Skholl, 1972, Cervulus sinensis Hilzheimer, 1905, Sus enganus Lyon, 1916, Cervus pygargus Pallas, 1771, Cervus lachrymans Milne-Edwards, 1871, Sus Linnaeus, 1758, Cervus reevesi Ogilby, 1839, Sus goramensis De Beaux, 1924, Muntiacus Rafinesque, 1815, Sus natunensis Miller, 1901, Sus nicobaricus Miller, 1902, Sus niger Finsch, 1886, Sus papuensis Lesson & Garnot, 1826, Sus ternatensis Rolleston, 1877, Sus tuancus Lyon, 1916)", "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present", { "or" : [ "GadmGid is ALB", "GadmGid is AND", "GadmGid is AUT", "GadmGid is BEL", "GadmGid is BUL", "GadmGid is BIH", "GadmGid is BLR", "GadmGid is CHE", "GadmGid is CYP", "GadmGid is CZE", "GadmGid is DEU", "GadmGid is DNK", "GadmGid is ESP", "GadmGid is EST", "GadmGid is FIN", "GadmGid is FRA", "GadmGid is GBR", "GadmGid is GRC", "GadmGid is HRV", "GadmGid is HUN", "GadmGid is IRL", "GadmGid is ISL", "GadmGid is ITA", "GadmGid is LIE", "GadmGid is LTU", "GadmGid is LUX", "GadmGid is LVA", "GadmGid is MCO", "GadmGid is MDA", "GadmGid is MKD", "GadmGid is MLT", "GadmGid is MNE", "GadmGid is NLD", "GadmGid is NOR", "GadmGid is POL", "GadmGid is PRT", "GadmGid is ROU", "GadmGid is RUS", "GadmGid is SJM", "GadmGid is SMR", "GadmGid is SRB", "GadmGid is SVK", "GadmGid is SVN", "GadmGid is SWE", "GadmGid is TUR", "GadmGid is UKR", "GadmGid is VAT", "GadmGid is XKO" ] } ] } The dataset includes 478259035 records from 16804 constituent datasets: 1 records from Sea Turtles of Dominica (aggregated per 1-degree cell). 7837 records from Finds of rare species of animals in Ukraine (2022). 83298 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 35 records from Ferme éolienne de ST JEAN DE LIVERSAY - Données biodiversité_Faune_St Jean de Liversay. 314 records from CardObs : Observations naturalistes issues de l'outil CardObs-Données saproxyliques de l'association Renard réalisées dans le cadre de l'atlas de Seine-et-Marne 2007. 1 records from Contributions to the taxonomy, identification, and biogeography of the Palaearctic species of Cymodusa Holmgren (Hymenoptera: Ichneumonidae: Campopleginae). 4 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 47 records from Waldstück Bremerhagen LK Bio Kl. 12. 15 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Inventaire des mammifères du Parc de la Haute-Île (93). 1 records from The neotype designation for Podismopsis gynaemorpha Ikonnikov, 1911 (Orthoptera: Acrididae). 8 records from Projet de construction d'un site logistique - Inventaire insectes. 145 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de SOULARD Gabriel. 2 records from Cadre d'acquisition personnel de Cathala Gael - Jeu de données personnel de Cathala Gael. 4 records from On some “ Hemicyclopora ” Norman, 1894 and “ Escharella ” Gray, 1848 species (Bryozoa, Cheilostomatida) from the Atlantic-Mediterranean region. Re-examination of their generic status and description of new species and a new genus. 2706 records from Plan de gestion de la Réserve Naturelle Régionale de la Massonne - Inventaire de données. 529 records from Water Framework Directive Lake Macrophyte Status Survey Data 2007 to 2019. 59 records from DOSSIER DE DEMANDE D’AUTORISATION ENVIRONNEMENTALE - Usine de transformation de produits laitiers - Données biologiques. 140 records from Bannwald Burghauser Forst. 903 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Bulletin du Muséum d'Histoire Naturelle [1895- ]. 29295 records from SEWBReC Bees, Wasps and Ants (South East Wales). 290 records from Données du Comité Départemental de Protection de la Nature et de l'Environnement de Loir-et-Cher (CDPNE) - Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 3678 records from Rote Liste Myriapoda Import 2022. 77 records from Sorensen distance for herbivores. 39 records from Projet de parc éolien SEPE La Blanche Côte - Données biodiversité liés au projet éolien de Vanault le Châtel - chiro ballon. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 7692 records from Parc éolien de Melleran, Lorigné, Hanc et La Chapelle Pouilloux - Données brutes de biodiversité suivi parc éolien MLHCP. 263 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Florent HERVOUET. 16 records from Cadre d'acquisition personnel de DUFRECHOU Willy - Jeu de données personnel de DUFRECHOU Willy. 15 records from Artenvielfalt des "Grünen Klassenzimmers". 605 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 982 records from Parc éolien Mont de la Grévière 2021 - Mont de la Grévière - suivi post implantation de parc éoliens - 2021. 900 records from 2015_GRENHA_2. 115 records from Plan de gestion 2017 - 2021 du site des Landes humides de Mazerolles (64) mené par le CEN Nouvelle-Aquitaine - Observations d'odonates (imagos) réalisées par le CEN Aquitaine selon le protocole STELI. 86 records from [CartoDyn] - Suivi reproduction. 5 records from Inventaire biodiversité du site Pierre Fabre d'Aignan. 985 records from Projet de parc éolien de Cap Estève - Chiroptères - écoutes en hauteur. 325 records from SACOI3 - Inventaires Faune et Flore terrestres. 22248 records from InfoFaunaFVG monitoring and surveillance network. 1191 records from Collections of Bioclass, school #179, Moscow. 214 records from Projet de nouvelle ligne sur le Centre de Valorisation Energetique de Villers Saint Paul - Données naturalistes - CVE Villers-Saint-Paul. 41369 records from Mammalia (Luomus). 622 records from Centrale de Production d'Energie Renouvelable de BENA - Bena_CHIRO_Alti. 7 records from Parc éolien de Clanlieu - Suivi mortalité 2020 - Clanlieu. 73 records from ZAC Dame Blanche Nord - Garges-lès-Gonesse (95) - Données biodiversités de l'étude d'impact ZAC Dame-Blanche. 38 records from CardObs : Observations naturalistes issues de l'outil CardObs - Inventaire des Octocoralliaires des fonds sédimentaires de la région niçoise. 2 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 5 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 2015 records from 07-Boralexforetdebauzon - Projet éolien de la Forêt de Bauzon études flore et chiroptères 2016/2017. 449 records from Données biodiversité Envol environnement Sablière SABCO du Haut-Pitois. 4 records from Plan de gestion 2016 - 2020 du site des Coteaux de Saint-Victor et Montagrier (24) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 146 records from Projet éolien des Muids - Données biodiv Eole des Muids Envol Environnement 2021 - Entomo. 1266 records from KUO Diptera collections. 91 records from Centrale solaire Les Echudes. 49 records from Pollen analysis of sediment profile TR0 from Truennensee. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 34 records from parc éolien de Linghem 2 - autre faune. 45 records from Expertise écologique du Golf Lyon Tassin en 2021 - Donnees espèces - Expertise écologique Golf Lyon Tassin 2021. 47 records from Projet de centrale photovoltaïque au sol du Massif de l’Etoile - Oiseaux - Inventaire non protocolé. 7 records from Données mammifères (hors chiroptères) - projet de parc éolien du Bosquel. 228 records from Mesures compensatoires sur des projets de Collectivités territoriales - Données CEN L-R Compensation collectivités. 3 records from Evolution of nuptial-gift-related male prosomal structures: taxonomic revision and cladistic analysis of the genus Oedothorax (Araneae: Linyphiidae: Erigoninae). 1 records from Redescription and phylogenetic assessment of Helicometra antarcticae Holloway & Bier, 1968 (Trematoda, Opecoelidae), with evidence of non-monophyletic status of the genus Helicometra Odhner, 1902. 18 records from Naturtag. 17 records from données espèces - Expertise IPE - La Machine - 2012. 79 records from 2020_SMIAGE_2. 9 records from RN12 - Déviation d'Ernée - Mammifères terrestres - Données opportunistes. 160724 records from Inventaire des oiseaux nicheurs de France métropolitaine 2009-2012 - Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 4 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de BLANC Josselyne. 4 records from Chaoborus flavicans Meigen (Diptera, Chaoboridae) is a complex of lake and pond dwelling species: a revision. 249 records from Monitoring of colonial waterfowl species (2013-2014). 3 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 988 records from SHF | POPReptile (Espaces protégés de la LPO France et de l'OFB) - POPReptile | RNN Moëze-Oléron. 10 records from Parc éolien de Clussais-la-Pommeraie - Données biodiversité du suivi environnemental - année 2020. 6510 records from ZFMK Orthoptera collection. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 28 records from Centrale Photovoltaïque de Poitiers-Biard - Inventaire des insectes. 39 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 152 (N.S) n°45 (2), 2017 - Données faune. 155 records from RN 164 - Mise à 2x2 voies dans le secteur de Rostrenen (section Loméven - Plouguernevel) - Projet de mise à 2x2 voies de la RN164 (Rostrenen). 115 records from Parc Eolien Bourbriac Nord - Chiroptères. 1105 records from Wintering wildfowl in Portugal – 1992-1993. 4657 records from European stag beetle monitoring network: transect observations. 23 records from Projet éolien du Camp Thibault - CT - Avifaune Migration Postnuptiale 2019 Inventaires Complémentaires. 37 records from Création d'un plateforme de préparation de biomasse et de Combustibles Solides de Récupération (CSR) à Rogerville (76) - Insectes - Inventaire non protocolé. 975 records from 2022_Ecosphère_1. 268 records from Parc éolien de Novion-Corny faune flore. 36 records from DMNS Egg Collection (Arctos). 137 records from Suivi écologique d'exploitation du parc éolien "Les Landes energies" - Données naturalistes du suivi environnemental - année 2020. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 1 records from Happywhale - Humpback Whale in Arctic Ocean. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 6 records from Aménagement d'un échangeur entre l'A36 et la RN1019 sur la commune de Sévenans - Suivi du passage à faune 2019 - Zone A. 6 records from The diversity of the genus Aricidea (Polychaeta: Paraonidae) from the Sea of Marmara, with descriptions of two new species and two new records for the Mediterranean fauna. 418 records from ONF - MIGBIO Observations et inventaires MOA ONF - ONF - MIG 2022 COA Saint Palais Chiroptères inventaire. 121 records from Orthoptera - SMF. 5460 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 414 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (3), 2009 - Données faune. 40 records from Opération d’aménagement du Domaine des Sources - SCCV LE VALLON DES SOURCES - mammifères. 6 records from Projet éolien de Bertaignemont - Mammifères terrestres 2018 Bertaignemont. 2 records from A practical introduction to microbial molecular ecology through the use of iChips. 9 records from Projet de construction d'une chaudière biomasse/CSR pour alimenter en énergie un réseau de chaleur urbain et industriel - Reptiles - Inventaire non protocolé. 966 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 58623 records from Parc éolien de Saint-Ambroix Est - Chiroptère SM3. 15 records from 2020_Pierrick GIRAUDET_1. 622 records from Parc agrivoltaïque de cellettes (16) - Oiseaux - Inventaire. 137 records from Expertise ecologique du Golf Club du Val de l'Indre en 2019 - Donnees espèces - Expertise Golf Club du Val de l'Indre 2019. 745 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2010 - 2014 Coordonnées GPS Lambert 93. 11 records from Centrale Hydroélectrique de Port à l'Anglais. 410 records from PARC EOLIEN DU MOULINET - MOULINET-Avifaune-Inv.-Points. 12 records from Parc éolien du Houarn - PE du Houran - Etude des chiroptères. 3302 records from Suivi du Pélobate cultripede sur les espaces protégés de la LPO France et de l'OFB - Suivi Pélobates cultripèdes automnal | RNN Marais d'Yves. 1 records from Cadre d'acquisition personnel de DURRIEU Lucie - Jeu de données personnel de DURRIEU Lucie. 184 records from Plan de gestion 2017 - 2021 du site des Coteaux du Légal (24) mené par le CEN Aquitaine - Observations ornithologiques (Indice Ponctuel d'Abondance) réalisées par Vya Natura (étude de l'avifaune nicheuse). 39 records from Données dans le cadre de l’extension de la ZAC de la Maladière - Etude du castor sur le marais de Bourgoin. 8 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Thorsen ANDRONIK. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 86158 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Données protocolées et non protocolées de Coléoptères issues des des differents projets de recherche de l'INRAe (ex. CEMAGREFF - IRSTEA). 61030 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 470 records from 59 - Beau Gui Avifaune. 10 records from Extension du parc d'activités économiques de la Novialle-Gergovie. - Avifaune - Novialle. 93 records from Arkolia Wind Park I - Suivi Environnemental 2019 / 2020 - Suivi environnemental - Parc éolien Ormoy - 2019. 8 records from Parc éolien du Pays Jusséen - Suivi de l’activité chiroptérologique en nacelle – Pays Jusséen – année 2019. 120 records from BIRDRACE The early birds. 2 records from Projet de construction d'une usine SNF de production de polyacrylamides - Extrait de la base de données SIRF pour le groupe des Rhopalocères. 288 records from FLHM Chaoboridae collection. 2125 records from Regroupement d'études et d'inventaires - Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 1248 records from RECORD Orthoptera Data. 70 records from ONCFS Réseau Ours brun - Ours 2010 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 74 records from Parc éolien de la Haute Borne - Données mortalité et suivi chiroptérologique en nacelle. 1 records from Parc Eolien de Inter deux bos MET - Suivi mortalité MET - Cadavre 11 éolienne MET01. 23 records from CardObs : Observations naturalistes issues de l'outil CardObs - Sortie de service PatriNat 2022 : Laonnois. 7 records from 52 - Parc éolien de Riaucourt Darmannes - 52 - Riaucourt - Mortalité 2020. 2560 records from Upper Silesian Museum, Bird Observations. 546 records from Parc éolien de Ally-Mercoeur - Sauivi de l'avifaune migratrice. 716 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de Quentin ROME. 479 records from SEWBReC Springtails and allies (South East Wales). 1 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 667 records from RN57 – Déviation Est de Vesoul - Données faune RN57 Vesoul. 59 records from Artenvielfalt auf dem Schulgelände. 1552 records from 2020_Société du Canal de Provence_1. 6573 records from 2020_Parc National des Ecrins_2. 2 records from National Museum of Natural Science. 416 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 5 records from Champ Chardon. 21872 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Alain Noël. 64 records from Suivi de mesures compensatoires RD45 - Chiroptères 2019. 105 records from Parc éolien de Beaufou - Eolien Beaufou suivi 2021. 69 records from BIRDRACE Pfeifenten. 2 records from Revision of the genus Lindholmiola HESSE, 1931 (Gastropoda: Pulmonata: Helicodontidae). 9 records from Création de la halte de Sainte Musse - Données Faune Halte de Sainte Musse. 41 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 147 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Laurence Beauchamp. 117 records from Ladybirds of Ireland. 47 records from Collections ichtyologiques et herpétologiques (BOUM). 273 records from Cadre d'acquisition personnel de Ttravers William - Jeu de données personnel de Ttravers William. 60 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 14722 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de Bruno OGER. 78 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Anna Even. 8 records from The InBIO Barcoding Initiative Database: Ypsolopha milfontensis, a new species from the Portuguese coast (Lepidoptera: Ypsolophidae). 129 records from Erfassung des Biotop- und Artenpotentials auf dem Muschelkalkplateau zwischen Nennsdorf, Oßmaritz und Göschwitz. 23 records from projet de prolongation d'exploitation et de modification de remise en état d'une carrière par remblayage partiel avec des matériaux inertes - Communes de Jumièges et Le Mesnil-sous-Jumièges - Amphibiens - Inventaire non protocolé. 5 records from Regroupement d'études et inventaires - Suivi Pies-grièches. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 377 records from Inventaires et suivis faune - Inventaire et suivi des libellules – Protocole STELI. 5 records from Die Bachspezies 2008/2009. 6 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 4657 records from Atlas of Bats from Continental Portugal 2013. 45643 records from Données Faune Base SIRFF - FNE Centre-Val de Loire - Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 5361 records from Réseau de suivi des macro-invertébrés aquatiques - Inventaire et suivi Macroinvertébrés. 23 records from Programme de connaissance des mammifères - [MAMMIFERE] - Chèvres férales - Suivi. 5 records from Streuobstwiese. 660 records from Western Australian Museum provider for OZCAM. 43 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 23287 records from NRW Regional Data: South East Wales Non-sensitive species. 65 records from [SUIVI] 2018 inventaire annuel parc éolien de Cabalas - [SUIVI] 2018 mortalite avifaune chiroptere cabalas. 274 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Joana PERRODIN. 2 records from Cadre d'acquisition personnel de Lacaze Rachel - Jeu de données personnel de Lacaze Rachel. 968 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Merle noir 2012 - 2016 Coordonnées GPS Lambert 93. 185 records from Projet de renouvellement urbain du quartier Mas de Mingue à Nîmes - Données brutes de biodiversité-Mas de Mingue-Nîmes. 62 records from ONF - Données issues d'études conventionnelles commandées par organismes exterieurs à l'ONF - MOA : APRR - ONF - APRR - Jean GOMEZ. 21 records from Waldstück am Schullandheim Bad Bederkesa. 1297 records from 2022_LPO PACA_8. 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 320 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes d'Olivier DELZONS. 314 records from Naturalis Biodiversity Center (NL) - Diptera. 1 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Monique CASTEX. 106 records from BIRDRACE Bon(n)apartemöwen. 17 records from Plant-parasitic nematodes of Republic of Karelia. 104 records from Réseau Loup - Lynx ONCFS - Lynx 2002 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 7814 records from Parc éolien Sameole Bois du Goulet - Chauves-souris - Points d'écoute. 26 records from FERME ÉOLIENNE DE BLANZAY - Avifaune Blanzay hiver 2017. 11 records from Plan de gestion 2013 - 2017 du site des Coteaux de Pujols (33) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 155 records from Parc éolien en mer de Fécamp - Eoliennes Offshore des Hautes-Falaises - Données état de référence_Mégafaune marine avion. 406 records from Données CPIE Touraine Val de Loire - Données CPIE 37 - STERF - 2020. 21 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 537 records from Parc éolien du Blanc Mont - Suivi chiroptère du parc de blanc Mont 2020. 274027 records from ARABEL - Arachnologia Belgica. 125983 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 217 records from Heinersdorfer Sumpfwiese. 177 records from Projet éolien de Bersac-sur-Rivalier - BSR - données petite faune. 2 records from Aménagement de la liaison A26/RN42 et diffuseur de Lumbres - Relevé chiroptères: Aménagement de la liaison A26/RN42. 258 records from Centrale éolienne Entre Saône et Salon. 8 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 3906 records from Arctic Species Trend Index (ASTI) : Marine. 106 records from Expertise dans le cadre d'une sollicitation liée à une étude d'impact - Données études d'impact CEN M-P. 736 records from 2022_ECO-MED_9. 16 records from MLZ Bird Collection (Arctos). 6 records from SOCIETE D'EXPLOITATION DU PARC EOLIEN LE MONT D'HEZECQUES - Suivi de mortalité - Mont d'Hézecques - 2021. 31 records from Naturschutzgebiet Müchelholz (Mücheln). 31 records from Wiese am Waldrand (Gurtweil). 88 records from Veille écologique - Suivi des papillons de jour. 3282 records from Historical information about the biodiversity of the "Askania-Nova" nature reserve (Kherson region, Ukraine). 141 records from Ferme éolienne de Monterfil - Avifaune migration postnuptiale. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 310 records from Parc éolien des Loups - Données mortalité et suivi chiroptérologique en nacelle parc les Loups. 279 records from Inventaire et atlas des Hyménoptères Pompilidae du Massif armoricain et des départements voisins - Atlas des Hyménoptères Pompilidae du Massif armoricain et des départements voisins : prospections 2018. 1294 records from Midden-Limburg Fish Ponds Survey. 262 records from Renouvellement et extension d'une carrière alluvionnaire à Rouvres-en-Plaine et Marliens (21) - Inventaire faune-flore Rouvres. 171 records from Demande de renouvellement et d'extension d'autorisation de carrière au titre de la rubrique 2510 des ICPE - Carrière de Villemanoche (89) - Donnees biodiversite carriere Villemanoche 181210. 6 records from ICPE - Suivi environnemental du parc éolien "Vihiersois" - Suivi de l’activité chiroptérologique en nacelle de V1 – Vihiersois – 2021. 8 records from Herbarium Senckenbergianum (FR) - Fungi. 6478 records from National System of Protected Areas in Poland - Animals. 6887 records from 2017_Yoann BLANCHON_2. 325 records from Plan de gestion 2016 - 2020 du site du vallon du Clamondé (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 65 records from Suivi environnemental du parc éolien du Quint (2019-2020) - Suivi post-implantation du parc éolien du Quint en 2019-2020. 903 records from CardObs : Observations naturalistes issues de l'outil CardObs - Geometridae de France métropolitaine. 13 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 430 records from 2013_DREAL PACA - N2000 - Parc Naturel Régional des Alpilles_2. 2183 records from Projet de centrale photovoltaïque au sol sur la commune de Vireaux (89) - Projet de parc photovoltaïque au sol sur la commune de Vireaux (89). 25 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 30 records from Installation d'une centrale photovoltaïque au sol sur une partie de l'ancien centre d'enfouissement de déchets (ISDND) de SUEZ RV sur la commune de PAGNY-SUR-MEUSE - Données Avifaune hivernante du projet PV de PAGNY SUR MEUSE. 16678 records from Suivi Temporel des Libellules (STELI). 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 18 records from Cadre d'acquisition personnel de karimjooy Sylvain - Jeu de données personnel de karimjooy Sylvain. 2225 records from Données des suivis des mesures compensatoires sur le site de Campanos. 23 records from Empididae of Ireland. 14 records from Contournement Est de Roissy - Etude faune/flore 2016-2017 d'ALISEA SARL pour le projet CER - Insectes. 13 records from Projet de parc éolien sur la commune d'Envronville - Données faune terrestre. 814 records from Ferme éolienne de Quesnoy-sur-Airaines 3 - Suivi chiroptérologique, avifaunistique et de mortalité du parc de Quesnoy III. 1290 records from Diversity of Spiders from Azorean Trails. 31 records from Mission forêt : le Sonneur à ventre jaune - Données de la quête INPN Espèces : Mission forêt, le Sonneur à ventre jaune. 99 records from Inventaires et suivis programme Lagunes mené par le Département des Landes - Ensemble des données Orthoptères. 6121 records from United Kingdom National Whale Stranding Database 1913-2008. 125 records from Projet éolien de Comps-Lagrand'ville - Oiseaux migrateurs - Inventaire non standardisé. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 36768 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Christophe CHAMBOLLE. 2 records from Parc éolien du Plateau de La Perche - Reptiles - Inventaire non protocolé. 74 records from Parc photovoltaïque de Montaut - PV Montaut faune flore 2022. 69 records from Pollen profile RAC20, Lake Racou, France. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 11 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Laurent ROUSSERIE. 11 records from A New Perlodes Species And Its Subspecies From The Balkan Peninsula (Plecoptera: Perlodidae). 71 records from Centrale hydroélectrique de Gavet. 4 records from Projet éolien des Bruyères - Inventaire des reptiles. 90 records from Centrale photovoltaïque au sol sur la commune de Perpignan (66). 90 records from Base BOMBINA du Parc Naturel régional Lorraine - Natura 2000 Vallée de la Seille. 2 records from Intraspecific variation and taxonomy of northern pika Ochotona hyperborea (Mammalia, Lagomorpha). 947 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pigeon ramier 2006 - 2010 Coordonnées GPS Lambert 93. 792 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases: Cliff-nesting Birds, priority conservation species: Complementary Observations - [2010-2014]. 53 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de NOBLECOURT Thierry. 709 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 10 records from Hydraena (s.str.) dinarica, new species (Coleoptera: Hydraenidae) along with further records of Hydraena spp. from Durmitor National Park, Montenegro and comments on the DNA barcoding problem with the genus. 5205 records from Rock ptarmigan road transect survey. 4 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 76 records from BIRDRACE Nachtigallen. 159 records from 2021_Syndicat Mixte du Massif des Monges_1. 1275 records from ConDidact Citizen Science Surveys - Amphibians 2007. 61 records from Inventaire des Lépidoptères Rhopalocères et Zygènes de France métropolitaine - Données de Midi-Pyrénées transmises par Pascal Peyrache.. 254 records from Plans nationaux d'Action (PNA) - Plan National d'Actions Pies-grièches. 14 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de THÉVENOT Jessica. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 403 records from [SUIVI] 2021-2022 Inventaire annuel du parc solaire de La Motte - Inventaire annuel du parc solaire de La Motte - 2021. 117 records from Inventaire chiroptérologique dans les Chataigneraies du PNRPL - Inventaire bioaccoustique et capture au filet de chiroptères en verger à châtaignes 2019. 27 records from Lucanidae. 90 records from Plan de gestion du Marais du Logit - Inventaire opportuniste Faune. 30 records from Projet de centrale photovoltaïque au sol de Fontenet 2 - commune de Fontenet (17) - Inventaire faune hors oiseaux et chiroptères. 2 records from Taxonomic review of the Oiketicoides species (Lepidoptera: Psychidae: Oiketicinae Acanthopsychini) from Anatolia, the Middle East and Central Asia. 235 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 124 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Occasionnelle du Loup en 2009. 52 records from Three endemic Aphaenogaster from the Siculo-Maltese archipelago and the Italian Peninsula: part of a hitherto unrecognized species group from the Maghreb? (Hymenoptera: Formicidae: Myrmicinae). 1 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) of Iran and adjacent territories. 2116 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Données de la collection de Hubert Piguet - Famille des Elateridae. 49 records from Parc éolien Eoles Yonne (Champ de la Vache et Galuchot) - suivi chiroptères parc Eoles Yonne 2019. 11431 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 9 records from Projet Courlis cendré et avifaune associée - Inventaire Avifaune. 1 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Avifaune Lande sèches. 249 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette lulu 2009 - 2013 Coordonnées GPS Lambert 93. 436 records from Centrale photovoltaïque au sol à Pargny sur Saulx - Données d'état initial de l'étude d'impact naturaliste. 1 records from Israel Sea Turtle Tracking Project 2008: Loggerhead & Green Turtles (aggregated per 1-degree cell). 90 records from Jurica-Suchy Nature Museum at Benedictine University Fossil Specimens (Arctos). 276 records from 2018_Parc National de Port Cros_10. 72 records from Atlas de la Biodiversité Communale - Acoustique chiro. 98 records from Projet éolien de Berceronne - Données brutes Chiroptères. 1 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 786 records from Projet éolien de Vallée de l'Arce extension - 2018 : Projet éolien de la Vallée de l'Arce - Chiroptères nacelle. 98 records from Parc éolien du Nilan (St-Sulpice-des-Landes nouvelle commune de Vallons-de-l'Erdre) - 44 - St Sulpice des Landes - Etude d'impacts - Chiroptères. 7 records from Projet de parc éolien de Teneur . - Données chiroptères 2019 - Teneur - transit automnal. 77 records from 2020_MAMP_1. 11009 records from Projet Eolien de Saint-Souplet - Données faune/Flore Parc éolien de Saint-Souplet. 282 records from Marine Turtles. 9 records from Parc éolien de la Voie Blériot Est - Données de mortalité 2020 parc éolien de Voie Blériot Est. 35 records from Animation technique des sites Natura 2000 ‘Barthes de l'Adour’ - Suivis rapaces 2019 - Site Natura 2000 des Barthes de l'Adour. 3 records from Projet de centrale photovoltaïque au sol de La Croix Lattée. 754 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle des bois 2011 - 2015 Coordonnées GPS Lambert 93. 444 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 173 records from demande de dérogation aux interdictions porté aux espèces protégées présentes sur le site de projets 1 et 2 portée par la SNC FP DONZERE, Parc des Eoliennes sur la commune de Donzère ( 26) - Oiseaux - Inventaire non standardisé.. 9 records from New Records Of Hoverflies (Diptera, Syrphidae) From Ukraine. I. Milesiini And Rhingiini. 34 records from Naturgrundstück (Eutin). 113 records from Influence of environmental factors on the distribution pattern of centipedes (Chilopoda) and other soil arthropods in temperate deciduous forests. 1 records from Coleção Entomológica Padre Jesus Santiago Moure (DZUP) - Hymenoptera. 228 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données arachnologiques de LEENKNEGT Virginie. 6 records from Projet de centrale photovoltaïque au sol - communes de Bénesse-lès-Dax et de Pouillon (40) - Parc PV de Pouillon - suivi environnemental. 4 records from 1ère phase d'animation (2017 - 2020) des Documents d’objectifs des sites Natura 2000 FR7200665 "Coteaux calcaires de Proissans, Sainte-Nathalène et Saint-Vincent-le-Paluel", FR7200672 "Coteaux calcaires du Causse de Daglan et de la Vallée du Céou" et FR7200676 "Coteaux calcaires de Borrèze" (24) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 68773 records from Données de la plateforme régionale SINP DREAL Bourgogne - Données de l'Observatoire de la Faune de Bourgogne. 10 records from Projet de centrale photovoltaïque au sol de la ZA de l'Etang Bertrand - Chauves-souris - Points d'écoute au sol. 246 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Perdrix rouge 2009 - 2013 Coordonnées GPS Lambert 93. 4 records from [SUIVI] 2020-Suivis environnementaux -Parc éolien de La Solerie - [SUIVI] 2020 mortalité avifaune et chiroptère parc éolien de la solerie. 229 records from Ferme Éolienne des Villes d'Oyses - Données brutes du suivi d'activité 2018 du parc éolien FEVO. 18 records from Plan de gestion 2017 - 2021 du site des neuf fontaines et de l'airial du Larousse (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 539 records from Phenological Center - Birds (Murmansk). 190 records from Parc Eolien Vallée du Moulin - Vallée_Moulin_Téléversement_données_biodiv_avifaune. 199 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 193 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette lulu 1996 - 2000 Coordonnées GPS Lambert 93. 2 records from Parc éolien de Scaër Le Merdy - 2020_Scaer_Le_Merdy_ecoute_chiro_nacelle. 6 records from Parc éolien de la Grande Combe - Suivi des chiroptères en nacelle - Grande Combe - 2021. 469 records from Grassland cartography SICONA, Recorder-Lux database. 40 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de CHARBONNEAU Adrien. 368 records from Biological Recording in Scotland - Bumblebee Survey. 123 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 2121 records from Biological Society of Northwest Jutland, field observations, Denmark. 13 records from Par éolien de Cambouisset - Corbières Méditerannée - Suivi automatisé activité chauves-souris 2014 - CAMB. 1 records from MVZ Herp Observations (Arctos). 155 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 1958 records from Bouresse Energies - Suivi avifaunistique post-implantation du parc éolien année 2 (2019-2020). 11 records from Plan de gestion 2013 - 2018 du site du coteau de Lembeye (64) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 72297 records from 2021_LPO PACA_7. 6 records from Plan de gestion 2017 - 2021 du site des neuf fontaines et de l'airial du Larousse (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 3 records from GEMFI HEUDEBOUVILLE - Amphibiens - Inventaire non protocolé. 3 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Séverine VITRAT. 1036 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 250 records from Données naturalistes d'Olivier LAURENT. 9 records from Télétransmission de données brutes de biodiversité parc éolien de Mancheville. 2 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 49 records from Natterjack Toads of Ireland. 82964 records from MnhnL various project records, Recorder-Lux database. 45 records from 2021_SOPTOM_1. 152 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 135 (N.S) n° 28 (4), 2000 - Données faune. 22 records from Site Condition Monitoring of dragonflies on Loch aí Mhuilinn SSSI potential extension - 2016. 124 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 6 records from Wuhle - Brücke / B1. 2 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 15 records from Plan de gestion 2016 - 2020 du site du domaine de Rodié (47) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 16 records from Phenological Center - Fishes (Murmansk). 6 records from CPENR de Barville-en-Gâtinais et Egry - Mammiferes terrestres. 7 records from Parc éolien d'Argonne - Argonne 2021 mortalité. 3 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 111 records from BIRDRACE Die Wendehälse. 57 records from Projet éolien des Bruyères - Inventaire des chiroptères (écoute active). 3 records from Cadre d'acquisition personnel de gaillard brigitte - Jeu de données personnel de gaillard brigitte. 3 records from Chauvé Energies - Amphibien - Inventaire non protocolé. 110 records from Suivi environnemental faune, flore. 367 records from Projet photovoltaique Saint-Martial d'Artenset 1 - Données brut - Saint Martial d'Artenset 1. 20 records from [SUIVI] 2022 - Exploitation de la carrière de la société EDILIANS à Cheminon (51) - Insectes inventoriés par ENCEM dans la carrière de Cheminon en 2022. 82 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 69 records from 2022_LPO PACA_12. 6180 records from NE Scotland fish records 1800-2010. 175 records from Projet de Parc Eolien de Mouchetune - Chiroptères actifs. 130 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 2008. 58357 records from Fichier communal des ongulés. 6 records from Sächsische Schweiz (Pfaffenstein). 13610 records from Faune Occitanie : Saisie naturaliste opportuniste - Données opportunistes OISEAUX de Faune-Occitanie. 43 records from Projet éolien de Saint-Barbant - Autre faune. 503 records from Programme les sentinelles du climat - effets du changement climatique sur la biodiversité en région Nouvelle-Aquitaine - Observations d'odonates réalisées par le CPIE Seignanx et Adour selon le protocole STELI adapté pour le programme. 19 records from Parc éolien de Lislet 2 - Avifaune migration prénuptiale Lislet 2. 75 records from PARC D'ACTIVITES LADILS - Données faune/flore dans le cadre d'un projet d'aménagement sur Bazas. 4 records from Living Cirripedia. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 1029 records from ConDidact Citizen Science Surveys - Spiders 2011. 28 records from Ferme éolienne du Vieux Chêne - communes de Beaurevoir et Serain (02) - Données avifaunistique Auddicé Vieux Chêne 2018 – Hivernage. 83 records from Parc photovoltaïque de Gramat - Parc PV de Gramat Suivi enviro 2021. 359 records from HogWatch Scotland Project - West European hedgehog records between 2019 and 2021. 37 records from Roter Berg Werdau (Leubnitz). 218 records from Land and freshwater molluscs of Northern Spain. 825 records from Ferme éolienne de Saint Médard d'Aunis - Projet Eolien_Saint-Médard-d'Aunis_Avifaune. 3785 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de Charlotte PICARD. 6 records from Téléversement données de biodiversité du parc éolien de Chassepain - Chauves-souris - Inventaire non protocolé - 2021. 6 records from Parc éolien Sameole Bois du Goulet - Suivi de l'activité chiroptérologique en nacelle - Ondefontaine - 2021. 5 records from University of California Santa Barbara Invertebrate Zoology Collection. 6447 records from Fish occurrence in Kama River basin. 76 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Neue Milbenarten aus Kärnten. 5528 records from CardObs : Observations naturalistes issues de l'outil CardObs - Observations naturalistes d'Hervé BRUSTEL. 1120 records from Entomology Collection at the Natural History Museum of Utah. 867 records from Étude des invertébrés sur les sites Natura 2000 de l'estuaire de la Gironde - Inventaire lépidoptère et odonate. 2175 records from Projet éolien des Portes du Porcien - avifaune. 211 records from Projet éolien de Flixecourt (SEPE La Croix Florent) - Oiseaux - Inventaire non standardisé. 5 records from Parc éolien de Clanlieu - Suivi de l'activité des chiroptères ICPE 2019 - Clanlieu. 114 records from BIRDRACE LiLaLau. 53 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Pierre DUCAMP. 1328 records from Fish occurrence in Kuban River basin. 17 records from Schulteich Freie Waldorfschule Darmstadt. 975 records from TWIC Spots and Stripes Public Survey. 10 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 96 records from Observatoire des sites majeurs - LEYRE - Inventaire et suivi Loutre d'Europe. 32 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 1927 records from Projet éolien des Noues - Inventaires toutes espèces. 1153 records from Inventaires et suivis programme Lagunes mené par le Département des Landes - Ensemble des données Odonates. 56 records from RN12 - Déviation d'Ernée - Oiseaux - Inventaire non protocolé. 14 records from Carrière des Etalins - renouvellement - Inventaires lépidoptères. 5 records from ZAC de la Guerche Sud - Inventaires des chiroptères. 77 records from Parc Photovoltaique de Sermaize-les-Bains - Données naturalistes. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 874 records from Parc éolien de Vallée Madame (Saisseval) - Suivi environnemental du parc de Vallée Madame 2018/2019 et 2020. 1422 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 41 records from ONCFS Réseau Ours brun - Ours 2006 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 12 records from Art´n Vielfalt im Kinderwald. 57 records from Observation of the cultivation of oyster larvae in the Spuikom Oostende in 1964. 448 records from Centrale éolienne de Trébry 2 - données brutes - Observation étude écologiques. 280 records from Invasive Non-Native Species, Outer Hebrides. 18 records from Phase 2 Lowland Grassland Survey of Wales. 6191 records from hymenoptera. 205 records from Naturalis Biodiversity Center (NL) - Crustacea. 509 records from Die Oligochaetenfauna zweier Ökosysteme auf Lößlehm unter Berücksichtigung der Auswirkungen von Chemikalienstreß. 2 records from Cadre d'acquisition personnel de DUCOS Pierre - Jeu de données personnel de DUCOS Pierre. 41 records from Suivi de chantier de la ligne du Revermont (39) - Oiseaux_inventaire. 1257423 records from CLICNAT- Base de données naturaliste picarde - CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 150365 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 125 records from Revision of Phoxinus in France with the description of two new species (Teleostei, Leuciscidae). 52 records from LABRUGUIERE ENERGIE_SUIVIS ENVIRONNEMENTAUX_2019 - LABRUGUIERE ENERGIE - suivi mortalité 2019. 5 records from Amélioration des connaissances des boisements gérés par l'ONF - ONF_Amélioration des connaissances en Forêt de Puntous. 219 records from Projet éolien des Trois Moulins - oiseaux. 5 records from Cadre d'acquisition personnel de GALERA Olivier - Jeu de données personnel de GALERA Olivier. 2 records from [SUIVI] 2021 - Exploitation de la carrière de la société BABOUILLARD Michel SARL - Mammifères - ENCEM - Coulmier-le-sec - 2021. 9600 records from SILENE-FAUNE-PACA - Ecosphère_2017_12_18. 6 records from Ceratophysella lobata sp. n. from Siberia with notes on C. brevisensillata Yosii, 1961 (Collembola: Hypogastruridae). 249 records from Fermanagh Flora. 50 records from Isle of Wight non-native invasive species. 1 records from Plan de gestion 2018 - 2022 du site de la Butte de la Lot (33) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 3 records from Exotic specimens butterflies at Museum Zoologi Bogor, Indonesia. 8001 records from Scotland Otter Survey Database. 11 records from GRAMENTES ENERGIE_SUIVIS ENVIRONNEMENTAUX_2021 - GRAMENTES ENERGIE - suivi mortalité 2021. 10 records from Parc PV flottant de Chateauneuf-du-Rhône - le Balafray - PV Flottant Chateauneuf du Rhône Le Balafray Données poissons 2018. 1332 records from Inventaire Entomologique, E. DECAUX 1998 - Inventaire des données récoltées par Emmanuelle DECAUX et la SEL. 67 records from Données Faune - Projet Human'Essence - Lacanau (33). 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Mathieu TAILLADE. 19 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 173 records from Parc éolien de Chaussée-César-Sud - Suivi activité chiroptères et suivi mortalité oiseaux et chiroptères - 2020 CCS. 2 records from Plan de gestion 2013 - 2018 du Lac de La Prade (33) mené par le CEN Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 143 records from Centrale photovoltaïque d'Aramon 2 - données bibliographiques faune/flore Aramon. 1591 records from Ornithological observations in the Kharkiv region of Ukraine. 137 records from CAS Entomology (ENT). 168089 records from Programme CarNET B (Cartographie Nationale des Enjeux Territorialisés de Biodiversité Remarquable) - Carnet B Lorraine. 67 records from Naturalis Biodiversity Center (NL) - Pisces. 2 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 1 records from Projet d'aménagement de la ZAC Les Minotiers à LE PONT DE CLAIX 38 800 (Isère) - Inventaire reptiles. 61804 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 72 records from Atlas de la Biodiversité Communales sur la Communauté de Commune de Montesquieu - Observations d'orthoptères (inventaire) réalisées par Locusta. 20140 records from Seasearch Marine Surveys in England. 12 records from Développement du pôle commercial de Peyssilieu (Meyzieu 69) - Inventaire lépidoptère_Meyzieu - Pôle commercial de Peyssilieu. 6 records from Projet éolien du Camp Thibault - CT - Chiroptères Transit automnal au sol Inventaires complémentaires 2019. 57 records from Swiss Occurrence Records of Native Species of Various Faunal Groups. 2963 records from Collection Trichoptera - SMF. 93 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 5281 records from Mutualisation des données naturalistes pour le rapportage Natura2000 en 2017 - Synthèse 10x10km des espèces de la Directive Oiseaux recensée par le Groupe Ornithologique des Deux-Sèvres de 2013 à 2017. 93 records from Projet éolien - Insectes - Inventaire non protocolé. 22 records from Occurrence of mammalia relicts at site Raj Cave. 1703 records from Parc éolien d'Orvilliers Saint Julien - Suivi chiroptères E1 2019 parc éolien Orvilliers. 77 records from Arizona State University Hasbrouck Insect Collection. 4716 records from Parc éolien du Chemin de la Ligue - Laprugne (03) - Données d'écoutes chiroptères nacelle - suivi environnemental 2020 LAP. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 137 records from Plan régional d'actions en faveur des odonates (PRAO) : 3ème phase (2017 - 2018) menée par le CEN Aquitaine - Observations faunistiques fortuites réalisées lors de journées de prospections animées par le CEN Aquitaine. 118 records from PARC EOLIEN DU MOULINET - MOULINET-Chiros-Inv.-Points. 114 records from 2021_SYMBIODIV_1. 305 records from Projet éolien "Champs Paille" - Données Brutes Faune-Flore. 193 records from Témoignages - [TEMOIGNAGE] - Regroupement de données tous règnes confondus. 49282 records from Projet éolien du Pays de Mayenne - Tous groupes. 17 records from Amtsrain Apolda-Zottelstedt. 128 records from Atlas communaux de la Biodiversité du Parc Naturel Régional des Landes de Gascogne (PNRLG) - Inventaire des reptiles 2014. 16 records from Projet éolien des Herbes Sauvages - Chiroptères été. 11 records from Inventaires et suivis effectués sur les retenues collinaires de l'Institution Adour - Inventaire sur la retenue collinaire de Renung. 7 records from An overlooked case for a century: taxonomy and systematics of a new Iberian species of Eumerus Meigen, 1822 (Diptera, Syrphidae). 402 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données de VINCENT Alexis (SAPROX). 20 records from [SUIVI] - 2021 - parc solaire - Reauville - VM_Engie_9110130_REAUVILLE_28_06_2022. 852 records from Parc éolien du Plateau de La Perche - Oiseaux - Inventaire non protocolé. 1154 records from Glasgow Museums BRC: Chrysomelidae. 7 records from Projet d'aménagement de la ZAC Les Minotiers à LE PONT DE CLAIX 38 800 (Isère) - Inventaire lépidoptères. 256 records from Projet d'aménagement de parc naturel paysager du Sempin, à Chelles (77) et Montfermeil (93) - Chauves-souris - Points d'écoute au sol - BIOTOPE. 56 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 102 records from Projet de parc éolien de l’Épinette Commune de Maisoncelle-et-Villers (08) - Inventaire faune et flore projet Maisoncelle-et-Villers. 1082 records from 2021_Alain SADORGE_1. 1 records from Myriatrix. 5 records from Données du suivi de la mortalité routière aux abords de l’ENS de l’étang de Fallavier. 70 records from Parc éolien de Haute Picardie - Données mortalité et suivi chiroptérologique en nacelle parc Haute Picardie. 2456 records from Gymnasium students as bat researchers. 100 records from Dossier de renouvellement d'autorisation d'exploiter une carrière - Saint Martin de Bréthencourt - étude faune / flore carrière Terres Salées (commune St Martin de Bréthencourt). 3 records from Parc éolien de Quatre Mesures - Insectes Inventoriés de manière fortuite sur l'aire d'étude rapprochée. 518 records from Centrale photovoltaïque de Lucy - Inventaires écologiques. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 429 records from The InBIO Barcoding Initiative Database: DNA barcodes of Iberian Trichoptera 01. 147 records from Site de tri, transit et regroupement de déchets d’activités économiques - CHIMIREC DELVERT - Données biologies CHIMIREC DELVERT. 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 83 records from Projet de parc éolien de Catillon-Fumechon - Données biodiversité - Catillon-Fumechon. 368 records from 2020_Agence MTDA_1. 3 records from [CartoDyn] - Enquête rapaces non rupestres. 728 records from GDR BioarchéoDat - Inventaires archéozoologiques et archéobotaniques de France. 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 133 records from EolMed - Gruissan, Ferme Pilote d'Eoliennes Flottantes et son raccordement au Réseau Public de Transport d'Electricité - Domaine maritime. 2601 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 1 records from Demande d'autorisation d'exploitation - SOREVO Environnement - Etude d'impact - SOREVO ENVIRONNEMENT 2019. 14 records from Occurrence of mammalia relicts at site Geißenklösterle. 4 records from Grand Paris Express - Centre d'exploitation d'Aulnay-sous-Bois - CE Aulnay_Etat initial faune flore (2018). 11123 records from Portuguese Moth Recording Scheme. 16 records from [SUIVI] Suivi post-implantation pour le parc éolien d'Espiers (mortalité). 16 records from Projet éolien des Herbes Sauvages - Chiroptères automne. 25 records from Parc PV d'Érôme-Gervans - Parc PV Erome-Gervans - Suivi biodiversité 2021. 430 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Etourneau sansonnet 2006 - 2010 Coordonnées GPS Lambert 93. 7 records from Projet de parc éolien de la Croix Guingal, sur la commune de Derval (44 590) - Croix Guingal - Chiro - parturition 2014. 622 records from Inventaires Odonatologiques de sites ENS du Pôle Nature de Vitrezay (St Sorlin de Conac) et de St Clément des baleines - Liste odonates 2 sites ENS Charente-Maritime. 854 records from Amphibia and Reptilia (Luomus). 489 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 25921 records from Données du Parc national des Cévennes - Inventaire et suivis d'espèces dans le Parc national des Cévennes. 6 records from Ferme éolienne de Saint Julien du Terroux - Suivi de l'avifaune - Parc éolien de Saint-Julien-du-Terroux - 2021. 79 records from Centrale solaire de Sigean Les Aspres. 794151 records from SEWBReC Birds (South East Wales). 8 records from Mise en souterrain partielle de la ligne électrique à 63 000 volts Aussois-Terres Froides - Mammifères - Inventaire non standardisé.. 7606 records from Lepidoptera of Mordovia State Nature Reserve. 264 records from Grand Paris Express - Ligne 17 Nord - L17N_Etat initial faune flore (2013_2016). 11 records from Collection Echinodermata SMF. 1 records from Projet éolien de la Plaine de Beaulieu - Données brutes Reptiles. 2 records from Cadre d'acquisition personnel de Creton Augustin - Jeu de données personnel de Creton Augustin. 5414 records from MfN - Fossil vertebrates IV. 15 records from Parc éolien de Pays de Retz Sud - [COMPLEMENTS] Suivi mortalité. 1959 records from Dipterists Forum: Field Week 1981 (Kent). 1228 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 625 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données arachnologiques de Corse par Canard A., Rollard C., Villepoux O.. 133 records from Suivi environnemental du Parc éolien du Valbin (10). 161 records from Données d'observation de la Faune, de la Flore et de la Fonge - [COPROPHAGE-CEFE] - Méthode d’inventaire moléculaire de l’entomofaune du sol en milieu pastoral d’altitude. 371 records from Projet éolien - Oiseaux - Inventaire non protocolé. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 97 records from Base BOMBINA du Parc Naturel régional Lorraine - Amphibiens filet/Marbotte-Ronval 2013. 117776 records from Amphibiens et Reptiles de France (Enquête 2). 2109 records from Dolichopodidae of Portugal - dataset 2009-2018. 1 records from Expertise dans le cadre d'une sollicitation liée à une étude d'impact - Données GSM Carrière Espeyran. 98 records from Parc Eolien "Les Eoliennes Citoyennes 11" - Beauvilliers - Les Villages Vovéens - LEC11_Avifaune. 1405 records from SEPE Fontaine le Sec - Chiroptères 2017-2018. 14 records from Contribution à la connaissance des Orthoptères – Locusta - Données opportunistes de Benoit DUHAZE. 1010 records from Butterflies of Ireland post 2021. 4193 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes d'Alain BERLY. 21983 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 62 records from A worldwide catalog of the Vermileonidae (Diptera: Brachycera). 332 records from Parc éolien d'Angerville les Pointes - suivi mortalité/fréquentation chiro. 310 records from Regroupement d'études et inventaires-Données opportunistes. 1118 records from Red-throated diver national surveys in Scotland - raw data. 367 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 20 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de LE GLOANEC Vincent. 41 records from Réseau Loup - Lynx ONCFS - Lynx 1999 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 21 records from Plan régional d'actions en faveur des odonates (PRAO) : 4ème phase (2019 - 2020) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine (Étude Leucorrhines). 54 records from Parc photovoltaïque du Parc d'Artillerie T1 - DONNEES_SINP.csv. 38 records from Parc éolien de la Grande Combe - Suivi des oiseaux - Grande Combe - 2020. 18206 records from River Biologists' Database (EPA). 9 records from PROJET ILE PORTE - Inventaire des poissons. 268 records from Demande d'autorisation environnementale pour la poursuite d'activité sur l'Ecosite de la Mélitée au lieu-dit "La Vergne" commune de Grand'Landes comprenant l'institution de servitudes d'utilités publiques (SUP) - Projet de prolongation d'activité, réhausse d'un centre d'enfouissement. 97086 records from Tiroler Landesmuseum Ferdinandeum. 1009 records from 2013_DREAL PACA - N2000 - Conseil Général 83_1. 2 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 7 records from Cadre d'acquisition personnel de Clerc Marion - Jeu de données personnel de Clerc Marion. 54 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 13864 records from Données de l'association Nature 18 - Données faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 8320 records from Odonata records from RSPB Reserves 1970-2009. 6 records from Données supplémentaires Atlas des Mammifères marins. 53 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 26 records from Données espèces - Expertise IPE - Sirac - 2014. 15 records from A huge undescribed diversity of the subgenus Hystricochaetonotus (Gastrotricha, Chaetonotidae, Chaetonotus) in Central Europe. 1328964 records from NBIS Records to December 2016. 716 records from Die Nordost-Alpen im Spiegel ihrer Landtierwelt. 127 records from Rohrmeistereiplateau und angrenzendes Gebiet. 2414 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 1199 records from Données acquises dans le cadre d'inventaire ZNIEFF - Données poissons et écrevisses / inventaires ZNIEFF ex-LR. 81 records from SILENE-FAUNE-PACA - Métropole_Nice_Côte_d'Azur_2017_12_18. 35 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 10 records from Projet de renouvellement et d'extension de l'autorisation d'exploiter de la carrière d'argiles de Pontigny - Inventaire des Odonates présents sur le site de Pontigny. 1930 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 8897 records from NE Scotland other invertebrate records 1800-2010. 5802 records from Centrale éolienne de Verdonnet-Jully - Télétransmission CE Verdonnet-Jully Chiro. 36890 records from [SUIVI] 2021 Suivis environnementaux parc éolien Miroir (80) - [SUIVI] 2021 - suivi chiroptère en nacelle - parc éolien Miroir. 2 records from Projet de parc solaire aux lieux-dits "Le Bois du Cerisier", "Les Fonteniers", "Le Reyteret" et "Les Planes" - [2018]_MAMMIFERES_Inventaire_BREZIERS_ENGIE. 137 records from Ermittlung und Bewertung der Depositionsbelastung zweier Buchenbestände im Kernmünsterland unter besonderer Berücksichtigung der Enchytraeen. 43 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 98 records from Regroupement d'études et inventaires - Données opportunistes sur les odonates. 123 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 67 records from Plan de gestion 2019 - 2023 de la Réserve Naturelle Régionale de l’Étang de Chourroumillas (64) mené par le CEN Nouvelle-Aquitaine - Observations d'odonates (imagos) réalisées par le CEN Aquitaine selon le protocole STERF. 11 records from 2017 Onwards Rare Invertebrates in the Cairngorms Shining Guest Ant Survey Data. 18811 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Données Entomologiques A. HORELLOU 1988-2022. 285 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 31 records from Parcs éoliens des 2 Moulins et du Catelet - 80 - Catelet&2Moulins - Suivi activité et mortalité 2018. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 315 records from EDIT - ATBI in Gemer area (Slovakia). 175 records from Projet de régénération et sécurisation de la ligne 878 000 Andelot la Cluse - Travaux 2021 - L878_Andelot La Cluse_REGE 2021_Inventaire faune/flore 2021. 328 records from Global compendium of Aedes albopictus occurrence. 325 records from Mollusques continentaux de France - Inventaire malacologique de la RNR des Marais de Stors. 39 records from Teich Berlin Wuhlheide. 5 records from Données brutes mortalité Parc éolien de Preuseville 2020. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 2 records from Projet pilote d'ombrière agrivoltaïque de Brouchy - Brouchy - Amphibiens. 17 records from AKG-Gelände (Bensheim). 115 records from Diagnostic écologique et élaboration d'une notice de gestion (prairies humides et calcaires) sur la commune de Monflanquin (47) menés entre 2017 et 2022 par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 909 records from 2019_Parc National de Port Cros_4. 79 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 7 records from Parc Eolien de la Vallée de Belleuse - BELLEUSE 2021 : écoutes en nacelle. 140 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données de coléoptère de DENIS Emmanuel (SAPROX). 9800 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 2718 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 46 records from Meetnetten.be - Transects for Eresus sandaliatus in Flanders, Belgium. 1168 records from RMQS biodiv. 49 records from Lebensraum Gesamtschule (Langerwehe). 14 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Kathy FOOT. 1459 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 4 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de Jean-Yves BOUTET. 428 records from Projet éolien de Flixecourt (SEPE La Croix Florent) - Oiseaux - Etude complémentaire. 939 records from Les Coléoptères Silphidés du département du Loiret. 1 records from Suivi du parc éolien de la Haute Borne 2020 - HAUTE BORNE Mortalité avifaune 2020. 118 records from BD de la plateforme partagée pour la diffusion des données naturalistes de Haute-Normandie - Observation des insectes sur le territoire de la Métropole Rouen Normandie. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 16 records from Hazel Dormouse in Ireland. 604 records from Parc éolien Gâtinais I - Inventaire 2021 parc éolien du Gâtinais 1 (77). 7 records from Projet de parc éolien de la Croix Guingal, sur la commune de Derval (44 590) - Croix Guingal - chiro - transit printanier 2014. 985 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Merle noir 1996 - 2000 Coordonnées GPS Lambert 93. 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 59120 records from Insects, Outer Hebrides. 3149 records from 2015_Parc National des Ecrins_1. 33 records from An der Ohm, (Wettsaasen). 185 records from Elaboration du DOCOB du site Natura 2000 ‘Réseau hydrographique des affluents de la Midouze’ (FR7200722) - Inventaire des odonates d'intérêt communautaire. 255 records from Elaboration du DOCOB du site Natura 2000 ’Réseau hydrographique du Midou et du Ludon’ (FR7200806) - Inventaire et regroupement de données Natura 2000. 12554 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 13 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 1997. 77 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Suivi naturaliste du Parc du Peuple de l'Herbe. 16 records from Aménagement d'un échangeur entre l'A36 et la RN1019 sur la commune de Sévenans - Suivi odonates 2021 - Zone C. 56 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Goncalves Cristina provenant de la base de donnée du SINP Île-de-France CETTIA. 103 records from 2020_Reynier Environnement_2. 26185 records from Données de Mammifères issues de Baznat. Midi-Pyrénées - Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 2 records from Suivi Cistude d'Europe du Bassin de stockage de Balanos - Données Cistude d'Europe du Bassin de stockage de Balanos. 401 records from KUO Mollusca collections (KUO). 1642 records from KUO Fish collections (KUO). 8 records from Ferme éolienne du Fourris - Inventaire des amphibiens. 104625 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 416 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Caille des blés 2008 - 2012 Coordonnées GPS Lambert 93. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 25 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 138 (N.S) n° 31 (1), 2003 - Données faune. 25 records from Projet d'aménagement de la ZAC du Saut du Moine - LEPIDOPTERES - TEREO - OBSERVATION DIRECTE. 3855 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de Loïc SALAUN. 1 records from MfN - Fossil plants (Paleophytic). 814 records from Projet de parc éolien de la Croix Dorée - Inventaire avifaune 2019-2020 - IPA et observations. 872 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle turque 2003 - 2007 Coordonnées GPS Lambert 93. 2172 records from EDP Foz Tua: Terrestrial Birds (transects) - Ecological Monitoring Program [2009-2012]. 166 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive littorne 2002 - 2006 Coordonnées GPS Lambert 93. 1939 records from East Ayrshire Species Database. 100 records from Euroants. 12 records from Parc éolien de Criel énergies - [COMPLEMENT] Données mortalité 2021. 12 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from Plan Aquitain d'Action Sonneur à ventre jaune - PRA Sonneur à ventre jaune - étude de répartition. 702 records from Données DREAL Centre-Val de Loire - Données Stage Arthur MORIS 2019 - PRA Papillons. 60 records from [SUIVI] 2019-2022 - Exploitation de la sablière de la société Sablière OESCH à Lingolsheim (67) - Faune inventoriée par ENCEM sur la sablière de Lingolsheim en 2022. 3402 records from Collection Crustacea - ZMB. 47 records from Suivi et déplacement d'amphibiens pour la construction de la liaison RD656/RD119 et des carrefours associés (Amorce de la rocade Ouest d'Agen) - Suivi Amphibiens dans le cadre du chantier. 105115 records from Rapportage 2013-2018 au titre de la directive Habitats-Faune-Flore - Données de synthèse Espèces issues du rapportage au titre de la directive Habitats - période 2013-2018. 1 records from RNR CGA Plan de gestion 2017-2021 - RNRCGA- Lézard catalan - Suivi - 2017-2021. 12 records from CPENR de Barville-en-Gâtinais et Egry - Barville_Chiropteres_Protocole_Mat_réparé. 3 records from Pentastira eminei sp. nov. (Hemiptera, Fulgoromorpha, Cixiidae) from Türkiye and notes on other Pentastira spp. in Türkiye and the Middle East. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 1 records from Cadre d'acquisition personnel de Daufresne Tanguy - Jeu de données personnel de Daufresne Tanguy. 1909 records from Dépose canalisation 5'' tubing - Chiro PE. 1 records from Parc éolien d'Argillières - hérpétofaune. 1912 records from Arques. 166403 records from Fife Nature Records Centre combined dataset. 798 records from Plan régional d'actions en faveur des odonates (PRAO) : 3ème phase (2017 - 2018) menée par le CEN Aquitaine - Observations d'odonates réalisées lors de journées de prospections animées par la LPO Aquitaine. 41 records from Etude préalable au plan de gestion des lagunes d'Hourtin pour la protection des sites à leucorrhines menée entre 2015 et 2019 par le CEN Aquitaine - Observations faunistiques (suivi par point d'écoute) réalisées par le CEN Aquitaine. 35 records from Naturschutzgebiet Lochbusch-Königswiesen. 822 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 209 records from Projet de requalification du Chemin du Carreau de Lanes - Données biodiversité - Données brutes de bio diversité liées au projet de requalification de voirie. 53 records from Plan de gestion 2017 - 2021 du site des Landes humides de Mazerolles (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 272 records from BIRDRACE Niederlausitz-Team. 1268 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - L'Amateur de Papillons. 6 records from Revisions to the faunas of Andrena of the Iberian Peninsula and Morocco with the descriptions of four new species (Hymenoptera: Andrenidae). 236 records from Suivi avifaune 2018 du parc éolien de Lusignan. 1 records from Echinodermata collection of Shirshov Institute of Oceanology. 1076 records from Projet de parc éolien de Saint-Symphorien-sur-Couze - Données biodiversité du projet éolien de Saint Symphorien sur Couze. 248 records from RD 963- CONTOURNEMENT DU LOUROUX–BECONNAIS. COMMUNE DE VAL D’ERDRE AUXENCE (49) - Données faune-flore RD963 Contournement du Louroux Beconnais. 2 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Damien TROQUEREAU. 46 records from Inventaire avifaune migration postnuptiale Vallée Joie. 9 records from Projet de Gravière à Autreville-sur-Moselle (54) - Données odonates Autreville-sur-Moselle 2015. 364 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 36 records from Projet éolien de la Haute-Voie (51) - Parc éolien de La Haute-Voie - inventaires entomologiques. 38 records from Centrale Photovoltaïque au sol de Salles - Données CNPN Salles. 13 records from Projet éolien de Burey - Données chiroptères en période de parturition, SM4BAT-FS. 15328 records from Projet éolien de Quatre Chemins - Projet éolien des quatres chemins (61) - Données Faune/Flore Ecosphere 2019. 6 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 13 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Mollusques - Inventaire non standardisé - FRAPNA74 - 24HNAT. 377 records from SILENE-FAUNE-PACA - CG04_2017_12_18. 719 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 11 records from Collection Ephemeroptera - SMF. 4 records from A new species of Contarinia (Diptera: Cecidomyiidae) from flower galls on the relict tree Zelkova abelicea (Ulmaceae) endemic to Crete (Greece). 524 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 406 records from Parc éolien de Fresnoy-Folny - Données Suivi ICPE Ecosphère 2019. 7974 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 11 records from Projet éolien de la Tène - Inventaire des Lépidoptères. 844 records from Denver Museum of Nature & Science - Entomology. 3 records from Carrière de sables et graviers sur la commune d' Abzac lieu-dit "La Communauté" - Données CNPN ABZAC. 3 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Marc GAGNE. 65 records from Projet du parc éolien de la Voie des Prêtres 2 - Liste de l'avifaune recensée en période de reproduction en 2010 et 2011. 1210 records from Some finds of birds, mammals, amphibians and reptiles in autumn and winter 2021 - 2022 in Kharkiv region, Ukraine. 111 records from 2018_LPO PACA_2. 96 records from Données de la quête INPN Espèces : Je crois que j’ai vu… Une Rosalie !. 4509 records from Eoliennes des Capucines - données chiroptérologiques du mât de mesure. 150 records from Programme les sentinelles du climat - effets du changement climatique sur la biodiversité en région Nouvelle-Aquitaine - Observations d'odonates réalisées par la Réserve naturelle nationale de l'Étang Noir selon le protocole STELI adapté pour le programme. 1 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1 records from Données herpétofaune - projet de parc éolien du Bosquel. 166 records from Renforcement de l’alimentation électrique de la vallée de la Neste - Données Faune/Flore IEA - Vallée de la Neste. 115 records from Strathclyde badger sett surveys 1996-2000. 343 records from Evaluation des MAEC - Inventaire Oiseaux sur les prairies en MAEC. 82 records from Parc technologique "Bas Carbone" - [réutilisation] 2021 suivis naturalistes sur PBC. 9 records from Parc éolien de Chigné - Eolien Chigné Mortalité 2021. 1928 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 5 records from New taxonomic and faunistic data on the genus Zodarion Walckenaer, 1826 (Araneae: Zodariidae) in the Balkans, with the descriptions of two new species. 3470 records from 2013_DREAL PACA - N2000 - Parc Naturel Régional du Queyras_1. 138 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 5 records from Parc Eolien le Mont D'Annelles - 2020 - Suivi des chiroptères en nacelle E3B. 381045 records from Atlas des papillons de jour et des libellules du Languedoc-Roussillon - Données CEN L-R papillons/libellule. 4 records from VFD-H: Heidenrod: Pferdeweide Mürth. 1696 records from 2018_Muséum de Toulon et du Var_1. 368 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Julien PIOLAIN. 18 records from Données du Centre de la mer de Biarritz. 68 records from Nottekanal, Klasse 7 - 10. 7 records from Amoeboid protists isolated from ancient Siberian permafrost. 4 records from Parc éolien du Mont de Bagny II - Inventaire de la flore sur l'aire d'étude. 20 records from Télétransmission de données brutes de biodiversité parc éolien de Mancheville. 2 records from First record of Bruchidius apicipennis (Heyden, 1892) (Coleoptera, Chrysomelidae) from Siberia. 4679 records from Inventaire des Mollusques Sphaeriidae de France. 9 records from Swedish Malaise Trap Project (SMTP) - Bethylidae. 17073 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données arachnologiques de CORNIC Jean-François. 714 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette des champs 2000 - 2004 Coordonnées GPS Lambert 93. 86 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Suivi de la flore patrimoniale de la RNR de Saint-Assise (77) dans le cadre d'un stage de M2. 15 records from Données espèces - Expertise IPE - Pontarlier - 2015. 2979 records from Suivi réglementaire arrêté Abaissement Partiels de la Retenue de Verbois - Inventaire flore et faune Haut-Rhône 2016-2019. 8 records from A taxonomic revision of the Palaearctic members of the Formica rufa group (Hymenoptera: Formicidae) - the famous mound-building red wood ants. 19 records from Monitoring of invasive alien species by the Province East Flanders, Belgium. 260 records from Extension et modernisation du Terminal 1 de l'aéroport Marseille Provence - Inventaire faune. 15 records from Flora und Fauna im Brexbachtal. 2695 records from MICROBIS database. 43 records from 2021 - Demande d'autorisation environnementale pour l'extension et le renouvellement de la carrière de la société Saviane Frères sur la commune de Beaunotte (21) de matériaux calcaires - Oiseaux inventoriés par ENCEM sur la carrière de Beaunotte en 2018. 178 records from Fauna marina de la costa vasca - Sistema de Información de la Naturaleza de Euskadi. 123 records from Birdrace-Professorenteam-Münster. 6 records from 2021_LPO PACA_24. 457 records from MoJ BioBlitz August 2018. 564 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2005 - 2009 Coordonnées GPS Lambert 93. 12 records from Ferme éolienne de Benet 2 SAS - Suivi et protection des populations de busards 2021. 362 records from Centrale solaire Les Canebières - suivi 2022. 84 records from Plan de gestion 2019 - 2023 de la station botanique du Normandin (33) mené par le CEN Nouvelle-Aquitaine-Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1168 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 11 records from Plan de gestion 2013 - 2017 du site de la Butte de la Lot (33) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 5 records from suivi environnemental du parc éolien citoyen de Béganne, Bégawatts , mortalité. 31 records from Inventaire avifaune hivernage Vallée Joie. 4 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Joël BRIED. 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 25 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 393 records from CardObs : Observations naturalistes issues de l'outil CardObs - CD95 - Recherche du Vertigo de Des Moulins et du Vertigo étroit sur les ENS du Marais de Baillon, de l’Étang de Vallière, du Marais du Moulin Neuf et du Ru de Presles. 72 records from Parc éolien des Champs Saint Pierre - Diagnostic avifaune hiver Champs St-Pierre à Laverrière. 9 records from Les Eoliennes du Coquelicot 1 - Coquelicot 1 - Suivi mortalité 2020. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 157 records from PROJET DE LA CENTRALE PHOTOVOLTAIQUE AU SOL DE SAUVIGNY-LES-BOIS - Projet PV Sauvigny-les-Bois 2 – Autre faune. 38 records from Dorfrand Mauderode. 522 records from parc éolien de SEEO Société d'exploitation éolienne d'Orvilliers - Suivi faune-flore 2016-2017 parc éolien Orvilliers-St-Julien (10). 61 records from Shrews of Poland. 1 records from Diagnostic écologique - Confortement de glissement de terrain RD36 PK 9+150 lieu dit « Pentone » - Mammifères - inventaire non standardisé. 269 records from Connexion L1-L2 de tramway et Centre technique et d'exploitation de Babinière - Données Faune Flore Ingerop 2018-2019. 7091 records from Appel à projet pour la connaissance naturaliste - Informatisation de la collection d'Alain Cama. 446 records from Données inscrites dans la campagne POCOROCH de 2018 - Littoral du Trégor. 31 records from STELI 2015 Saint-Pée-sur-Nivelle (64) par l'association EcoGIS. 30 records from ONCFS Réseau Ours brun - Ours 2004 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 74 records from Projet d'aménagement situé Route de Seine, à Cormeilles-en-Parisis (95) - Insectes - Inventaire non protocolé. 5 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 14 records from Cuxhavener Küstenheiden. 1521358 records from Hatikka.fi observations. 6 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 1504 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de Monsieur JOURDE Rémi. 843 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Geai des chênes 2008 - 2012 Coordonnées GPS Lambert 93. 6 records from Suivi mortalité et activité chiroptères sur le parc éolien de Bouhy. 124684 records from inatura - Erlebnis Naturschau Dornbirn. 4 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 6 records from Parc éolien Nibas IV (Croix) - 80 - Croix - Suivi activité et mortalité 2019. 331 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données de coléoptère de RAEMDONCK Hugo (SAPROX). 104 records from ABC de Sumène - Atlas de la Biodiversité Communale sur la commune de Sumène. 302 records from New data on species diversity of Annelida (Oligochaeta, Hirudinea) in the Kharbey lakes system, Bolshezemelskaya tundra (Russia). 65 records from Parc Eolien d'Apremont - Données biodiversité Apremont. 26 records from Coleção Entomológica Padre Jesus Santiago Moure (DZUP) - Coleoptera. 25 records from Projet photovolta¨ïque de Tour de Faure. 9 records from Two new species of the previously monospecific genus Guipuzcosoma Vicente & Mauriès, 1980 from Spain, with establishment of Guipuzcosomatidae fam. nov. (Diplopoda: Chordeumatida). 666 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 1 records from CardObs : Observations naturalistes issues de l'outil CardObs - Bulletin d'informations de l'Association française de Lichénologie. 6 records from Port de plaisance Isle Adam - Inventaire des chiroptères par détection acoustique. 36 records from Projet de centrale photovoltaïque au sol SVR. 61 records from Ferme éolienne de Saint-Hilaire-du-Maine - Insectes patrimoniaux observés durant les expertises entomologiques en 2014. 7926 records from WTSWW Data: All Taxa (West Wales). 56 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 6 records from Pollen record of profile 3TZ. 12 records from Checklist of water mites from mainland Portugal and its archipelagos. 26 records from "Ahrschleife bei Altenahr". 502 records from South Australian Museum Adelaide provider for OZCAM. 106 records from 2020_NATURALIA_3. 68 records from Projet d’entrepôt logistique et de son siège social sur la commune d’Izon (33) - Données biodiversité sur cycle biologique. 360 records from Parc éolien du Chemin d'Avesnes - Ecoute en altitude 2021 : éolienne E15. 39 records from Parc éolien de l'Argillière - 80 - Rouvrel - Busards+Avifaune 2019. 2 records from Cadre d'acquisition personnel de vacilotto olivier - Jeu de données personnel de vacilotto olivier. 47 records from Unter hellen Zinnen und finsteren Grotten. 4 records from Projet éolien de Comps-Lagrand'ville - Amphibiens - Inventaire non standardisé.. 8 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 2366 records from Base BOMBINA du Parc Naturel régional Lorraine - Modernisation des ZNIEFF du PnrL. 1 records from Projet éolien de Raillimont (02) - Relevé opportuniste de données sur les oiseaux. 1 records from Projet de parc photovoltaïque de Charentonnay - Charentonnay - Flore. 613 records from 2021_LPO PACA_13. 2 records from Occurrence of mammalia relicts at site Niederlehme. 1264 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Grand Voyeux - Suivis scientifiques. 223 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 5 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 138 records from Tasmanian Museum and Art Gallery provider for OZCAM. 15 records from Occurrence of mammalia relicts at site Veternica. 6 records from Parc éolien de Choqueuse-les-Bénards - Suivi de l’activité chiroptérologique en nacelle – année 2019. 101 records from Centrale Solaire ENGIE PV GUELTAS - inventaire faune flore. 2 records from Unexpected high species richness of Bythotrephes Leydig, 1860 (Branchiopoda: Cladocera: Cercopagididae) in subalpine Austrian lakes, with the description of new taxa. 8 records from SOCPE DE LA VALLEE DU MOULIN - [SUIVI] Suivi post-implantation Vallée du Moulins (mortalité). 31 records from Champ Photovoltaïque RANCOGNE 2 sur les Communes de Pranzac et Moulins-sur-Tardoire - Inventaire des chiroptères (sol). 726 records from Suivi environnemental du parc éolien de Mazeray et Bignay - Oiseaux - Protocole de suivi environnemental des parcs éoliens terrestres. 55 records from Protocoles - Faune aquatique - [FAUNE AQUATIQUE] - Pêche electrique ObsOcc (A trier !). 970 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Observations et collection de Coléoptères d'Alain Sadorge. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 152 records from Biodiversity of Luiz Saldanha Marine Park. 3 records from Renouvellement et extension de la carrière "les Chails" commune de Geay - Inventaire mammifères. 53095 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 19 records from Occurrence of mammalia relicts at site la Grotte des Eglises. 30 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 18603 records from Chrysomelidae beetle data from iRecord. 317 records from 2016_Parc Naturel Régional du Verdon_6. 38 records from CAMBON_ENERGIE_SUIVIS ENVIRONNEMENTAUX_2021 - CAMBON ENERGIE PLANESIE - suivi mortalité 2021. 190 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) The Arctic University Museum of Norway. 496 records from Bureau d'étude _ Endemys - Alcedo Marché ZNIEFF 2018. 1 records from Cadre d'acquisition personnel de Chauvin Lisa - Jeu de données personnel de Chauvin Lisa. 196 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 756 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2009 - 2013 Coordonnées GPS Lambert 93. 563 records from 2016_Société du Canal de Provence_1. 220 records from Mica - Muskrat, Raccoon and Coypu occurrences collected by ITAW in Germany. 81 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 27 records from Parc éolien de Saint-Généroux - 2021_Saint-Généroux_Suivi mortalité. 5 records from Parc éolien de Villesèque - Suivi de l'activité des chiroptères 2018 - Villesèque. 5 records from Pollen record of profile 3TZ2. 3941 records from Données naturalistes faune-flore projet éolien La Faye 2 extension. 650 records from The results of synchronous surveys of birds in the wetlands of the Azov-Black Sea region of Ukraine in August 2018. 174 records from Projet de parc éolien de la Croix Dorée - Inventaire avifaune 2016 - Observations. 187 records from Buret - Suivi post implantation parc éolien - 53 - Buret - Suivi activité avifaune 2018. 31 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 9 records from Aménagement d'un échangeur entre l'A36 et la RN1019 sur la commune de Sévenans - Suivi des passages à faune 2021- Zone A et C. 35 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 69 records from Feral Pigs - Sightings and Cull records - 2014-21. 8781 records from 2018_AAPOPG_1. 5 records from Plan de gestion 2019 - 2023 du site des Grottes de Sare (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 7102 records from Données de la Réserve Naturelle Nationale de Chérine (36) - Données privées RNN Chérine - Faune 2019. 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 75 records from Expertise ecologique du Golf Blue Green Saint Laurent en 2015 - Donnees espèces - Expertise Golf Blue Green Saint Laurent 2015. 363 records from Otter survey of Ireland 2004 & 2005. 209 records from Centrale solaire photovoltaïque au sol de La Dominelais - Dominelais_projet photovoltaïque_données faune flore 2020. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 133688 records from Suivi Temporel des Rhopalocères de France (STERF). 223 records from Site Industriel et Portuaire de Salaise-Sablons - Aménagement d'une plateforme logistique, réalisation de son raccordement routier et ferroviaire, et création d'un quai fluvial - Inventaire faune et flore Salaise quai. 3 records from Confirmation of Gonioctena rufa (Kraatz, 1879) (Coleoptera: Chrysomelidae) in northeastern Asia, previously misinterpreted as a subspecies of G. viminalis (Linnaeus, 1758), and a new synonym in the genus. 1230 records from Projet BiodiverCité - Données protocolées Odonates. 325 records from PE des Quatre Chemins - Données MNHN Quatre Chemins Avifaune - Migration automnale. 10 records from Landwehrbach. 105 records from Projet BiodiverCité - Données opportunistes de Frédéric Revers récoltées lors des prospections terrains. 12 records from Projet éolien Val de Vingeanne Est - Inventaires complémentaires mammifères. 229 records from Eoliennes des Pivoines - Données Faune/Flore. 26 records from 2021_BIOTOPE_8. 1 records from Regroupement d'études et inventaires - Suivis botaniques. 485667 records from Swiss National Grasshoppers Databank. 22 records from Suivis spécifiques des poissons migrateurs en Occitanie - Suivi du Saumon Atlantique par l'Association Loire Grands Migrateurs (LOGRAMI). 79 records from Grand Rhinolophe et trame verte bocagère en Poitou-Charentes - Données sur les colonies de reproduction et d'hivernages des chiroptères de Charente-Maritime. 84531 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 8 records from MONTAGNOL ENERGIE_SUIVIS ENVIRONNEMENTAUX_2020 - MONTAGNOL ENERGIE - Suivis 2020 - Mortalité. 5 records from Pollen profile II/B at Krumbach, Germany. 33912 records from Weevil and Bark Beetle records via iRecord. 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 144 records from Projet d'extension de la carrière de la Tranquillité sur la commune de Saint-Christophe-du-Ligneron. 7 records from Nationalpark Harz Schul-AG Braunlage. 13 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 1 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Gérard LALANDE. 38 records from Was lebt in der Brutzwiese?. 636 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (2), 2009 - Données faune. 57 records from Stigmella stettinensis (Nepticulidae) specimen data. 22 records from Autorisation 2021-33 - Université Exeter. 82 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de Pierre-Alexis RAULT. 14 records from Projet d'aménagement de parc naturel paysager du Sempin, à Chelles (77) et Montfermeil (93) - Insectes - Inventaire non protocolé - EGIS. 299 records from Parc éolien de Gaillefontaine (Surelle) - 76 - Gaillefontaine - Surelle - Etude d'impacts. 1281 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Avifaune Lande sèches. 373 records from Expertise IQE - Drambon 2021. 298 records from 2020_Amis des Marais du Vigueirat_3. 307 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 5 records from Contribution to the knowledge of the genus Boucheona (Oligochaeta Hormogastridae) in France with a newly described species and a redescribed species. 34 records from Ferme éolienne de la Queue d'Ane - Liste des espèces de chauves-souris inventoriées en point d'écoute au sol. 102 records from Programmes d'Atlas de la biodiversité communale (ABC) - Atlas de la Biodiversité Communale sur les communes de Montmaurin, Lespugue et Blajan - Haute-Garonne - Données du CEN MP. 332 records from Projet de parc éolien de Boussais - Données Faune Flore BOUSSAIS. 2916 records from 2022_Agence MTDA_1. 141 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes 2022 de Bruno DAUGET. 31 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 291 records from Programme immobilier de 138 logements répartis en 3 bâtiments - JDD Faune et Flore - récolte 2020 - Programme immobilier. 697 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette des champs 2012 - 2016 Coordonnées GPS Lambert 93. 845 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Grive musicienne 2006 - 2010 Coordonnées GPS Lambert 93. 85 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Mikaël PAILLET. 78 records from Projet éolien de la Montie - Autre Faune. 66 records from Suivis faunistiques du site du Moulin de la Ville - Suivi Amphibien - POPAmphibien. 14 records from Parc éolien de Villesèque - Suivi de l'activité des chiroptères 2017 - Villesèque. 485 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Hasrouni Sami provenant de la base de donnée du SINP Île-de-France CETTIA. 354 records from 2022_ECO-MED_6. 373 records from Données de l'association Epiméthée - Epiméthée - Données 2020-2021. 389 records from Collection ornithologique A. Maës. 51 records from Parc éolien des champarts - Les_Champarts_Chiroptères_Protocole_passif. 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 12 records from Suivi du Bouquetin ibérique Capra pyrenaica - Occurrences de Bouquetin ibérique (Capra pyrenaica) collectées par le PNP et le PNRPA. 694 records from Données de biodiversité parc éolien du Bois Clergeons Chiro audiomoth. 88 records from Eoliennes des Primevères - Eoliennes Violettes et Primevères - avifaune étude d'impact. 17 records from Örtzemündung (Stedden). 84 records from Parc photovoltaïque de Gramat - Parc PV de Gramat suivi enviro 2020. 81223 records from National Stag Beetle Surveys (Great Stag Hunts). 4 records from Mise en souterrain partielle de la ligne électrique à 63 000 volts Aussois-Terres Froides - Insectes protégés - Inventaire non standardisé.. 982 records from Die Collembolenfauna landwirtschaftlich genutzter Flächen in der Umstellungsphase von konventionellem auf ökologischen Landbau. 8 records from Marine Offshore Seabed Survey data held by JNCC. 117 records from Demande d'autorisation d'exploiter un Ecopôle de traitement et valorisation de déchets non dangereux - Faune - Inventaire non protocolé. 319 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de Monsieur LEFEBVRE François. 9872 records from Projet Eolien des Quatre Mesures - Mammifères inventoriés de manière fortuite sur l'aire d'étude rapprochée. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 1230 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Marquet Jacques provenant de la base de donnée du SINP Île-de-France CETTIA. 13 records from Occurrence of mammalia relicts at site Sütto_6. 34 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de BARNEIX Guilhem. 280 records from Projet de réhausse du lac de la Ganne - Insectes - Inventaire non standardisé. 18 records from Squalius cephaloides, a synonym of Squalius cii (Teleostei: Leuciscidae). 1004 records from Inventaire Odonates-Rhopalocères 1999-2002 du PNRLG - Données odonates. 17318 records from Swiss National Diplopoda Databank. 124 records from The results of synchronous mid-winter waterbird census of the Azov-Black Sea region (Ukraine) in 2017. 1 records from Type specimens of fungi. 25 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 108 records from Projet éolien de Frasne-le-Château - Avifaune (hors IPA) sur la zone d'étude du projet de Frasnes-le-Château. 14 records from Ruisseau Pré Poulain - PrePoulain_Odonates. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 1310 records from 2022_Communauté de Communes des Alpes d'Azur_2. 311 records from BIRDRACE Gätkes Erben. 23 records from Ferme Éolienne du Haut Plateau Picard - Données brutes du suivi de mortalité 2021 du parc éolien Haut Plateau Picard. 9 records from The genus Semicerura (Collembola; Isotomidae) in Asia. 71 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 75 records from Dépose canalisation 5'' tubing - Reptile Opport. 94 records from SUD VESOUL - Inventaires faune ZE restreinte 2020. 159 records from EDP Foz Tua Otter (Lutra lutra) [transects] - Ecological Monitoring Program (2011-17). 1909 records from Carabidae of the European North-East of Russia. 12 records from Les éoliennes de Conquereuil - Parc éolien terrestre de Conquereuil - Mortalité - 2020 - E3. 256 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 174 records from 2020_Reynier Environnement_1. 54 records from Parc photovoltaïque du Parc d'Artillerie T2 - DONNEES_SINP.csv. 1041 records from Données de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS 2015 Chiroptères, Maculinea, Cistude d'Europe. 35 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes d'Anaïs MAS. 33 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 65 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 229 records from Ferme éolienne de Lusseray-Paizay-Le-Tort SAS - Données naturalistes suivi environnemental 2020-2021 (année N3). 30 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 248 records from DEMANDE D’AUTORISATION ENVIRONNEMENTALE UNIQUE : Renouvellement d'activité de la carrière de la CAUNETTE - Etude d'impact AUDE AGREGATS Lastours 2016. 5462 records from Arachnids (Aranei, Opiliones) from grass stand and forest litter in the Urals, Russia. 2850976 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 18 records from SILENE-FAUNE-PACA - ALTERECO_2017_12_18. 106 records from Projet éolien de Cambaynart Est - Inventaires du volet naturel de l'étude d'impact. 186 records from 2020_Parc National de Port Cros_8. 17 records from Inventaire reptiles et amphibien INSPIRA 2021. 193602 records from Biofokus. 8534 records from Anymals+plants - Citizen Science Data. 909 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 1563 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 64 records from 2019 CNPN concernant l'extension du Centre Landais de Transit des Déchets Industriels (CLTDI) de Bégaar - Inventaire oiseaux réalisé par Simethis sur la zone d'extension du CLTDI (2019). 2578 records from Sierra Nevada Atmospheric-Pollen Data set (SNOWPOLL). 991 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste CARON Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 12 records from Happywhale - Humpback Whale in North Atlantic Ocean. 15 records from Parc éolien de Quincy-le-Vicomte 1 - [SUIVI] Suivi post-implantation pour le parc éolien de Quincy 1 (nacelle). 130879 records from ABV - Common breeding birds in Flanders, Belgium (post 2016). 1 records from SEANET (Seabird Ecological Assessment Network) - Powered by Anecdata.org. 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 16 records from Parc éolien de La Montagne Ardéchoise - Suivi mortalité ICPE 2018 - Montagne Ardéchoise. 531 records from Données entomologiques de Christian Cocquempot - Diptères Syrphidae d'Indre-et-Loire - données Christian Cocquempot. 6 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 3093 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 4 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 782 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle turque 1997 - 2001 Coordonnées GPS Lambert 93. 23 records from Ferme éolienne des Buissons SAS - Données suivi Avifaune par Auddicé de la Ferme éolienne des Buissons 2018-2019. 48 records from Pollen profile Märchenwald B, Harz, Germany. 3 records from Vespertilionidae. 1 records from New species and additional records of Cephalocousya and Drepasiagonusa from China and Russia (Coleoptera: Staphylinidae: Aleocharinae: Oxypodini). 3 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de Jean-Christophe DE MASSARY. 3 records from Dermaptera in the icipe collection. 32 records from Programmes d'étude et de conservation de populations d'espèces particulières (hors PNA et PRA) - Etudes sur le Flamant rose. 474 records from Parc Eolien de Saint Aubin du Plain - Inventaire Oiseaux. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 151 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pigeon colombin 2008 - 2012 Coordonnées GPS Lambert 93. 174 records from Projet photovoltaïque au sol de Menestreau - CHIROPTERES_MENESTREAU. 6 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Kevin CURTIL. 12 records from Parc éolien de Lislet 2 - Avifaune hivernage Lislet 2. 10 records from Inventaire 2019 parc éolien de la Guenelle WP France 1 (51). 142 records from Etude des insectes sur la Montagne de Saint-Maurice (ENS) à Dieulefit (26) : état des lieux et mise en place des protocoles - Coleo_sapro_Saint-Maurice. 1 records from Canary Islands - OAG (aggregated per 1-degree cell). 15 records from An annotated type catalogue of the centipedes (Myriapoda: Chilopoda) held in the Zoological Museum Hamburg. 7 records from Projet de Parc Eolien des Vallées - Chauves-souris - Points d'écoute sur mât de mesure -. 148 records from Construction du village Alzheimer à Dax (40) - Inventaire de la Faune patrimoniale. 16 records from Parc éolien d'Angerville énergies - [COMPLEMENTS] Suivi post-implantation. 1868 records from Parc éolien d’Andilly-les-Marais - Données biodiversité. 20 records from Life Vison d'Europe et espèces associées - Données de Vison d'Europe par piège-photo, capture ou indices indirects (empreintes...). 1356 records from Programme LIFE CROAA - Eradication de la Grenouille taureau : Piégeage. 217 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Anaelle WILLER. 5 records from Warnowufer Groß Klein. 99 records from Données biodiversité Projet éolien d'Ormesnil - Entomofaune. 5569 records from Meetnetten.be - Population counts for dragonflies in Flanders, Belgium. 30 records from Plan de gestion 2013 - 2018 du site du Coteau de Peymourel (24) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 44032 records from Alterra (NL) - Entomofauna inventory in peat swamps. 1 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 3298 records from Phenology and biological traits of migrating brown trouts and sea trouts sampled by trapping in the Nivelle river (France).. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 12 records from Suivi environnemental du parc éolien de Mazeray et Bignay - Mammifères - Protocole de suivi environnemental des parcs éoliens terrestres. 35 records from CPS Château Raymond - Biotope_OISEAU_INV2. 336 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Caille des blés 2012 - 2016 Coordonnées GPS Lambert 93. 70 records from Plan de gestion 2015 - 2019 du site du Coteau de Monco (33) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 14 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de LESSIEUR David. 57 records from Species inventories NP Öewersauer, Recorder-Lux Database. 31 records from "Schwarzwassertal" bei Pobershau. 4 records from ISDND Téting sur Nied : suivi écologique 2020 - Reptiles 2020. 78 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Amphibiens - Inventaire non standardisé - FRAPNA74 - 24HNAT. 538 records from Poursuite d'exploitation de l'ISDND de la Rape - CHIRO_POINTS_ECOUTE_SOL_SM5242_2016. 1170 records from Springtales from lichen communities at Kollåsen in Norway. 6 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 137 (N.S) n° 30 (1), 2002 - Données faune. 7 records from Cadre d'acquisition personnel de Roy Cédric - Jeu de données personnel de Roy Cédric. 4 records from Parc éolien de la Tardoire (Maisonnais-sur-Tardoire) - 87 - Maisonnais - Mortalité 2020. 134683 records from Activité générale du bureau d'étude BIOTOPE (1994 - 2013) - Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 5 records from Suivi écologique carrière "Ottengrund" - données amphibiens 2020. 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 474 records from Danielsberg (Mölltal, Kärnten). 3 records from FE DU BOIS DE MERDELOU_SUIVIS ENVIRONNEMENTAUX_2021 - FE DU BOIS DE MERDELOU - suivi mortalité 2021. 12964 records from SILENE-FAUNE-PACA - LPO_PACA_2017_12_18. 1 records from Construction d'un crématorium animalier - Inventaire mammifères 1. 24 records from ABC de Saint Roman De Codières - Atlas de la Biodiversité Communale sur la commune de Saint-Roman-de-Codières. 735 records from Targeting a portion of central European spider diversity for permanent preservation. 222 records from Parc éolien Les Nesloises - suivi activité chiroptères en nacelle. 1 records from Accompagnement des acteurs sous-trame urbain - périurbain - Urbaflore - suivis espèces remarquables - 2020. 43 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 87 records from Projet éolien de Lesquielles-Saint-Germain et Villers-lès-Guise - Oiseaux_Points d'écoutes. 193 records from Parc éolien de Saint-Ambroix Est - Chiroptère écoutes actives. 13 records from Suivi post-implantation du parc éolien de Cuxac-Cabardès en 2018/2019. 970 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Merle noir 2006 - 2010 Coordonnées GPS Lambert 93. 702 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Faisan commun 2009 - 2013 Coordonnées GPS Lambert 93. 1804 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 47 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 4 records from Évaluation environnementale - Projet d'aménagement Rives du Gave - Inventaire Chiroptère. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 679 records from 2019_Parc Naturel Régional du Luberon_2. 1 records from Plan de gestion 2016 - 2020 du site des Landes humides de Mouguerre (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 149 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 5 records from ICPE - Suivi environnemental 2020 du parc éolien "L'Epinette" - Mortalité avifaune. 1 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 2826 records from Collection Pisces SMF. 31637 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 203 records from Grand Paris Express - Ligne 15 Sud - L15S_Suivis faune flore 2019. 142 records from 2021_Parc National de Port Cros_5. 283 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 84 records from Projet de centrale photovoltaïque au sol de Garde-Colombe - Données avifaune. 2 records from Compensation écologique CDM de Versailles Matelots TRANSKEO T13 - Données faune Transkeo 2021 - points. 3 records from Cadre d'acquisition personnel de suhubiette benat - Jeu de données personnel de suhubiette benat. 64 records from Landschaftspflegehof (Berlin). 325 records from Projet SACOI EDF - EDF SACOI3. 208 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (4), 2011 - Données faune. 9 records from Bachpatenschaft Beeke. 242 records from CardObs : Observations naturalistes issues de l'outil CardObs - EPTBSGL_ANSE_ARCOT_2019. 462 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Plan de gestion 2019 - 2023 de la Réserve Naturelle Régionale des carrières de Tercis-les-Bains (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par la RNG Saucats - La Brède. 5365 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 1443 records from Projet éolien de Trizac - Chiropteres_T. 5 records from Diagnostic écologique sur le site Jardin sportif Promis (2019). 90 records from Artenvielfalt auf den Elbwiesen (Dessau). 4 records from parc éolien d'Allainville - suivi de l'activité des chiroptères en nacelle - parturition 2021. 1008 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de Daniel PAVON. 1 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 397 records from Projet de parc éolien du Saint-Varentais - Parc éolien Saint Varentais Energies - oiseaux. 1 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 280781 records from Estonian Nature Observations Database. 10 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 5 records from Suivi post-implantation parc éolien SPDM2 - Relevés Avifaune – auddicé – SPI à Saint-Pierre-de-Maillé 2. 1 records from ONF - Données issues d'études conventionnelles commandées par organismes exterieurs à l'ONF - MOA : CEMA - ONF - DFF Import Etudes LNEF_64_Thèse_Parmain - MOA : CEMA. 1 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 123 records from Ferme éolienne de Massay 2 SAS - Suivi activité avifaune. 7 records from NCSM Mammalogy Collection. 3 records from Mise en oeuvre des mesures compensatoires à l'aménagement du parc photovoltaïque d'Hourtin - Données opportunistes. 50 records from Ferme éolienne du Vieux Chêne - communes de Beaurevoir et Serain (02) - Données avifaunistique Auddicé Vieux Chêne 2018_Migration postnuptiale. 226 records from Nivå Bay species list, Zealand, Denmark. 16660 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 354 records from Tierökologische Untersuchungen in gefährdeten Biotopyten des Landes Sachsen-Anhalt 1. Zwergstrauchheiden, Trocken- und Halbtrockenrasen. 158 records from Projet éolien de l'Isle-Jourdain - Inventaires - Faune - CERA - 2016. 130 records from Carrière La Vigne et ISDI de Louët - Carrière La Vigne - ISDI de Louët - Faune. 13 records from Dossier de demande d'autorisation d'exploiter une carrière de matériaux alluvionnaires en eau sur les communes de Salles-sur-Garonne et Lafitte-Vigordane - Données Faune Flore. 696 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Faisan commun 2008 - 2012 Coordonnées GPS Lambert 93. 973 records from Projet Eolien des Quatre Mesures - Inventaire de l'avifaune sur l'aire d'étude rapprochée. 3089 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Mares. 6 records from Revision of the genus Canthocamptus (Copepoda: Harpacticoida) with a description of a new species from the Lena River Delta (North-eastern Siberia). 3 records from Parc éolien de Mont de bagny - Chauves-souris - Inventaire non protocolé - 2020. 2 records from PROJET D'AMENAGEMENT DU QUARTIER OSTERODE - Inventaire des reptiles ostérode. 899 records from Parc éolien de Saint-Généroux - 2020_Saint-Généroux_Suivi avifaune. 30 records from Suivi d’un serpent en danger : la Vipère péliade - Données de la quête INPN Espèces : Suivi d’un serpent en danger, la Vipère péliade. 5 records from Two new nematode species of the genus Tobrilus Andrássy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 30 records from Type locality records of Polycystididae species in the world. 5 records from Projet de parc éolien de la Croix Guingal, sur la commune de Derval (44 590) - Croix Guingal - Chiro - Transit automnal 2015. 1122 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de Stéphane ORIO. 4 records from Collection Echinodermata - ZMB. 60 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Suivi botanique et entomologique pour la gestion de la portée de RTE sur l'emprise de la RNN de Bassée. 14 records from SOCPE DE LA MARDELLE - [SUIVI] Suivi post-implantation pour la Mardelle (nacelle). 97 records from WildesMoor bei Schwabstedt. 613 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 2 records from Potamophylax idliri sp. nov. (Trichoptera: Limnephilidae), a new species from the Jastrebac Mountains in Serbia, with molecular and ecological notes. 258 records from RCE - Zooarchaeological reference collection. 212 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 700 records from Ökologische Untersuchungen der Collembolenfauna von verschieden bewirtschafteten Flächen am Niederrhein. 2 records from Projet d’élargissement à 2x3 voies de l’autoroute A4 sur le Contournement Nord-Est de Metz (CNEM) - Zones de présence d'espèces animales et végétales. 8 records from Bolbelasmus (Bolbelasmus) zagrosensis (Coleoptera: Scarabaeoidea: Bolboceratidae), a new species from Iran, along with an updated key to the western Palaearctic species of the subgenus. 257 records from Création d'un plateforme de préparation de biomasse et de Combustibles Solides de Récupération (CSR) à Rogerville (76) - Chauves-souris - Points d'écoute. 17 records from 2022_Pierre FRAPA_1. 23 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Suivi de la reproduction des Lamproies de Planer sur les sites Natura 2000 en Seine-et-Marne. 10 records from Molecular analysis of five controversial Balkanic species of Allolobophora (sensu lato) Eisen, 1873 (Lumbricidae, Clitellata) with emendation of the genus Cernosvitovia Omodeo, 1956. 14 records from 2019_CCVUSP_1. 81 records from 2018_CD04_1. 4 records from Cadre d'acquisition personnel de Cottet Lise - Jeu de données personnel de Cottet Lise. 539 records from Système d'Information sur la Nature et les Paysages d'Ile de France - étude entomologique de la ZSC du Bois de Vaires. 3974 records from Regroupement d'études et d'inventaires - Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 345 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 37364 records from Waterbird counts, Luomus dataset. 22 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" des saligues, (BORDÈRES-CAZÈRES-RENUNG). 235 records from Plan de gestion 2014 - 2018 de la Réserve Naturelle Régionale des carrières de Tercis-les-Bains (40) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 7 records from 44 - Parc éolien du Merisier (Ligné, les Touches) - 44 - Ligné - Mortalité 2020. 6 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 157 records from EXTENSION/RECONSTRUCTION DE LA STATION D’EPURATION DE CONDAT A LIBOURNE - Oiseaux - Inventaire non standardisé. 2500 records from 2022_Réserve Naturelle de Camargue_1. 105 records from Fish Fauna of Berlin. 3 records from Parc éolien du Beaujolais vert - Suivi mortalité ICPE 2021 - Beaujolais vert. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 233 records from 2017_LPO PACA_2. 255 records from Installation de traitement de déchets non dangereux - Préparation de biomasse - VALSUDDONNAT2. 360 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Arnaud Bak. 45 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Fannich Hills SSSI. 900 records from Collembola of forest tundra ecosystems of the Sula (Malozemelskaya tundra) and Bolshaya Rogovaya (Bolshezemelskaya tundra) rivers. 60788 records from Derek Lott Coleoptera Dataset. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 2 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 36 records from Ferme éolienne de Lion-en-Beauce - Autre faune (Entomofaune, Herpétofaune et mammifères terrestres). 284 records from PROJET EOLIEN DU CHAISEAU - Données Chaiseau MNHN. 17 records from Projet de parc solaire aux lieux-dits "Le Bois du Cerisier", "Les Fonteniers", "Le Reyteret" et "Les Planes" - [2016]_INSECTES_Inventaire_BREZIERS_ENGIE. 66 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 2497 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 16567 records from Censo de ardeidas invernantes y nidificantes de la Comunidad Autónoma del País Vasco. 6541 records from Likona Invertebrates. 80 records from Ferme éolienne d'Arnac sur dourdou - Avifaune. 22 records from Ferme éolienne des Hauts Près SAS - Hauts-Près (60) - suivi année 2 - mortalité 2020 oiseaux chiroptères. 2363 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 1 records from Suivi des conditions de franchisement des ouvraes de protection à la mer par les civelles et autres espèces en fonction des modes de gestion mis en place. - Inventaire et suivi. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 908 records from Données invertébrés saisies sous BioloVision Auvergne-Rhône-Alpes - Données saisies par FNE 74. 7248 records from DBRC Hemiptera species records 1969 to 2015. 92 records from SPS projet d'exploitation d'une carrière "La Marasse" à Martot - Données faune flore. 5 records from BB-Biodiversität a. 5 records from Collection Myriapoda - SNSD. 1779 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 44964 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 6 records from Notes on the subspecies of Plagionotus arcuatus (Linnaeus, 1758) with description of a new subspecies from Iran (Coleoptera: Cerambycidae). 1 records from Two new species of Plutomurus Yosii (Collembola: Tomoceridae) from the Caucasus and central Europe. 6153 records from Parc éolien de Pliboux - Suivi post implantation 2018 Pliboux. 622 records from Suivi d'activité sur le parc éolien de la Mutte (société ESCOFI) à Landifay-et-Bertaignemont (02) (année 2020-2021) - Suivi écologique parc éolien de la Mutte - 2020. 3480 records from Dorset SW Pilot species dataset. 1360 records from Mesures compensatoires autoroutes - Données mesures compensatoires ASF - ex région M-P. 2 records from First data on the bionomics of Leptochilus (Euleptochilus) limbiferus (Morawitz 1867) (Hymenoptera: Vespidae: Eumeninae), with taxonomic notes and new records. 154 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Philofauna provenant de la base de donnée du SINP Île-de-France CETTIA. 1280 records from Long-term monitoring of small mammals (abundance and distribution) in Doñana Natural Area 2011-2021. 194 records from Suivis faunistiques du site du Moulin de la Ville - Suivi Odonate - STELI. 107 records from Etude pour la restauration de la continuité écologique de la Sèvre Nantaise au droit de l’ouvrage de la Branle - Inventaire faune / flore. 20 records from Ferme éolienne de la Queue d'Ane - Inventaire des espèces de chauves-souris observées en altitude. 9868 records from Cumbria Non Native Invasive Species. 90 records from Regroupement d'études et inventaires - Inventaire et suivi de la faune écrasée. 319 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cairngorms SSSI. 18 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 66767 records from Natuurmuseum Brabant, Tilburg - Invertebrates. 80 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 305 records from Mammifères sauvages carnivores - base de données privées UR CPIE Pays de la Loire. 2 records from Projet photovoltaïque au sol de Menestreau - REPTILES_MENESTREAU. 31 records from Animation du Document d’objectifs du site Natura 2000 FR7200666 - Vallées des Beunes (24) menée par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 140 records from Projet éolien de Lemoncourt - Migration postnuptiale. 19 records from Plan de gestion 2017 - 2021 du site des neuf fontaines et de l'airial du Larousse (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 124 records from Programmes d'étude et de conservation de populations d'espèces particulières (hors PNA et PRA) - Données CEN M-P espèces. 143066 records from England Non Native Species records 1965 to 2017. 22 records from parc éolien des Trois Frères - Données brutes de mortalité suivi éolien du parc d'Aumelas trois frere. 7 records from Suivi Environnemental 2021-2022 Ferme éolienne des Tilleuls - Chiro à hauteur de nacelle 2021 Tilleuls. 148 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Claire BETBEDER. 72 records from Parc éolien de Vouillon - Données suivi mortalité 2019. 105 records from Projet éolien des Portes du Porcien - chiroptères. 657 records from Expertise IQE du Golf de la Rochelle Sud en 2018 - Donnees espèces - Expertise IQE Golf de la Rochelle Sud 2018. 2 records from PARC EOLIEN DE CHAMP BONNET - Données Amphibiens. 16 records from Demande d'autorisation environnementale - Ouverture d'une carrière - Inventaire chiroptères pour un projet de Demande d'autorisation environnementale. 287 records from Océanopolis mammifères marins en Bretagne 1993-2015. 936 records from Animation technique des sites Natura 2000 ‘Barthes de l'Adour’ - Animation des Docobs des barthes de l'Adour. 6727 records from 2018_Parc National des Ecrins_2. 78 records from Gronau - auf der Suche nach dem Neunauge. 474 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 19336 records from Eden Arthropod Azores Database. 14 records from Eoliennes des Violettes - Eoliennes Violettes et Primevères - flore étude d'impact. 2183 records from Thrips (Thysanoptera) in Norway. 9 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Emilien HENRY. 69 records from Entdeckertour am Muldestausee 1/05. 3129 records from Projet éolien de la Plaine de Beaulieu - Données brutes Oiseaux. 14 records from Cadre d'acquisition personnel de Cheylan Marc - Jeu de données personnel de Cheylan Marc. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 39 records from Observations of Rumina (Mollusca, Gastropoda) in the south-east of France between 2018 and 2022.. 122 records from SILENE-FAUNE-PACA - BIOTOPE_2017_12_18. 108 records from BIRDRACE Diesmal sehen wir mehr. 1030 records from Marine benthic dataset (version 1) commissioned by UKOOA. 4664 records from European Moth Nights. 172 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 248 records from Parc éolien Saint Secondin, lieu dit les Brandes - Parc éolien terrestre de Saint-Secondin - Mortalité - 2018. 873 records from Inventaire national des Crustacés Décapodes de France métropolitaine - Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 6779 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 16 records from Parc éolien de Champ-Feuillant - Données Busard 2018-2019. 1 records from CardObs : Observations naturalistes issues de l'outil CardObs-Données naturalistes de STON Daniel. 118 records from Virginia Polytechnic Institute and State University Insect Collection. 1 records from MfN - Micropaleontology. 515 records from BUND - Dassower See (Lübeck/Dassow). 68144 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de Monsieur François FOURNIER. 63 records from Birds and plant species near Petushki town (Vladimir region). 55 records from 2021_SEGED_1. 3 records from Cadre d'acquisition personnel de Ratié Audrey - Jeu de données personnel de Ratié Audrey. 9 records from Convention - Fondation d'Entreprise du Golf de Vidauban pour l'Environnement - Jeu de données convention FEGVE-SPN (numéro 2). 2 records from Sächsische Schweiz (Wehlener Gebiet). 4 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 336 records from Projet de parc éolien Lande du Moulin - LDM_Téléversement_données_biodiv_avifaune. 72 records from Projet d'extension des capacités industrielles Merck Biodevelopment - Etat des lieux environnemental TechnopoleMontesquieu. 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 8175 records from Heteroptera collections of SW Finland. 3 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 268 records from Données Brutes de Biodiversité Ferme Éolienne de la Lichère. 70 records from Pollen record of sediment core Bokanjacko Blato 1. 4 records from Contrat de Rivière - RIPARIAS: detection and management of aquatic invasive alien species. 662 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2006 - 2010 Coordonnées GPS Lambert 93. 15 records from Poursuite d'exploitation de l'ISDND de la Rape - AMPHI_INV_2016_2017. 84 records from Projet de parc phtovoltaïque au sol à Lubersac (19) au lieu-dit "les Gatouilles haut" - Inventaire faune-flore. 12 records from Eoliennes des Violettes - Eoliennes Violettes et Primevères - chiroptères mat de mesure. 17 records from Faune Occitanie : Saisie naturaliste opportuniste - Données oiseaux transmises par diverses structures (hors SINP). 6 records from Projet d'aménagement du port de La Turballe - Chauves-souris - Points d'écoute au sol. 36 records from SILENE-FAUNE-PACA - BIOMEO_2017_12_18. 1985 records from LES BOUCLES DU VINCOU - Avifaune. 59 records from Inventaires sur le réseau Aquitaine Nature du PNR Périgord-Limousin - Inventaire sur le site de la Pierre levée. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain). 27 records from Parc éolien de l'Argillière - 80 - Argillière - Suivi activité et mortalité 2019. 1464 records from Mammals in the collection of Zoological Museum of NSNHM (the National Science and Natural History Museum at the National Academy of Sciences of Ukraine, Kyiv): Erinaceidae, Talpidae, Soricidae, Myoxidae, Sminthidae. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 2379 records from CardObs : Observations naturalistes issues de l'outil CardObs-Données naturalistes de MATT Francis. 32 records from Projet de ferme pilote d'éoliennes flottantes du golfe du Lion et de son raccordement électrique - Oiseaux - Inventaire non standardisé.. 417750 records from 2019_LPO PACA_5. 104 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Conventionnement de la commune de Chepnier. 20 records from IMPLANTATION D'UNE USINE DE RECYCLAGE AUTOMOBILE ULTRAMODERNE - MOLINS CREAUTO. 92 records from MER BATIMENT A - Données faune et flore. 64 records from Projet éolien de Liernolles et Montcombroux-les-Mines - Avifaune_migration prénuptiale. 68 records from 2016_Parc Naturel Régional du Verdon_3. 1345 records from Weevils of Poland. 24 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 412 records from Envoi de données complémentaires disponibles à la SFEPM pour l'atlas des Mammifères de France - Données Loutre compilées par la SFEPM pour compléter les cartes de l'atlas national des Mammifères.. 1062 records from Projet éolien Murier - 59 - Murier - Avifaune. 1 records from Animation du Document d’objectifs du site Natura 2000 FR7200666 - Vallées des Beunes (24) menée par le CEN Aquitaine - Observations faunistiques (suivi par piège photographique) réalisées par le CEN Aquitaine. 11 records from New and confirmed records of fruit flies (Diptera, Tephritidae) from Italy. 675 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste RADOGEWSKI Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 40 records from A new semi-cryptic Filistata from caves in the Levant with comments on the limits of Filistata insidiatrix (Forsskål, 1775) (Arachnida: Araneae: Filistatidae). 2 records from Atlas communaux de la biodiversité du Parc Naturel Régional des Landes de Gascogne 2014-2020 - Inventaire de la flore du PNRLG 2016 (Gironde). 3 records from Parc éolien de Clitourps - Suivi mortalité ICPE 2014 - Clitourps. 225 records from Expertise IQE du Golf du Gouverneur en 2021 - Donnees espèces - Expertise IQE Golf du Gouverneur 2021. 1 records from Projet de centrale photovoltaïque au sol, dit "Centrale photovoltaïque des Aubargues sur la commune d'Istres - Flore - Inventaire non standardisé. 25 records from Royal Belgian Institute of Natural Sciences marine Chelicerata collection. 31 records from Appui technique et scientifique aux réserves naturelles (nationales et régionales) - Données ANA - CEN Ariège sur la RNR du massif de Saint-Barthélémy. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 798 records from Projet éolien Le Champ du Moulin commune de Lys Haut Layon (49). 27 records from New insights into the Enchytraeus albidus complex (Annelida, Enchytraeidae), with the description of three new species from seashores in Italy and Croatia. 76 records from Expertise Végétal local - Huiron 2020 - Données espèces - Expertise Végétal local - ZNIEFF des talus de la voie ferrée de Huiron à Vauhalaise. 195 records from Parc éolien de la Butte Noire - Butte_noire_Téléversement_données_biodiv_avifaune. 35 records from Pollen analysis of sediment profile BLA00 from Blankensee. 7 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes d'Olivier VILLEPOUX. 17 records from Two new species and additional records of the genus Geostiba Thomson, 1858 (Coleoptera: Staphylinidae: Aleocharinae) from Turkey. 6 records from NCSM Non-molluscan Invertebrates Collection. 74 records from Suivi Environnemental 2021-2022 de la Ferme éolienne du Lindier - Avifaune nidif 2021 Lindier. 28257 records from KUO Coleoptera collections (KUO). 475 records from 2022_Parc Naturel Régional du Luberon_1. 1 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 15 records from Projet éolien de la Tène - Inventaire des Orthoptères. 1376 records from Bird Monitoring 2017, Meise Botanic Garden. 82 records from Projet d'aménagement d'une zone artisanale intercommunale sur la commune de BRACH - Inventaire faune/flore. 613 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 32 records from Craigellachie NNR invertebrate records compiled from SNH files. 577 records from 2018_SSNATV_1. 95 records from Elaboration des DOCOB des sites Natura 2000 ‘Plateau d’Argentine’ (FR7200810) en 2009 et ‘Réseau hydrographique de la haute-Dronne’ (FR7200809) en 2010 - Inventaire et suivi Entomologique de Desmond KIME. 10 records from Plan de gestion 2020 - 2024 du site du Coteau de Casserouge (47) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 22 records from On the microphthalmous Lathrobium Gravenhorst species of Turkey II. Two new species, a new synonymy, and an updated key to Turkish species (Coleoptera: Staphylinidae: Paederinae). 38 records from Collection Polychaeta - ZSRO. 140 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste LUPOLI ROLAND provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Données nouvelles de fourmilions (Neuroptera, Myrmeleontidae) pour le bassin genevois. 37 records from Projet d’aménagement et de rénovation-construction sur le domaine d’Esclimont - esclimont_2018. 896 records from projet de prolongation d'exploitation et de modification de remise en état d'une carrière par remblayage partiel avec des matériaux inertes - Communes de Jumièges et Le Mesnil-sous-Jumièges - Chauves-souris - Points d'écoute. 23 records from Parc éolien de Remilly-Wirquin - Données suivi mortalité. 9561 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Tillier Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 33 records from Eoliennes des Althéas - Données Entomofaune. 72 records from Parc photovoltaïque de Montaut - PV Montaut faune flore 2021. 267 records from 2020_Muséum d'Histoire Naturelle de Nice_1. 310 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de Laurent PONCET. 9 records from Buret - Suivi post implantation parc éolien - 53 - Buret - Suivi activité chiroptères sol 2020. 2282 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 3 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Kévin LE FALHER. 6 records from Données brutes Mortalité Parc éolien des Longs champs. 210 records from UWBM Mammalogy Collection (Arctos). 4 records from A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae). 170 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données de Lépidoptères de Bruno DAUGET - Dépt du CHER (18). 5 records from Dossier de renouvellement et d'extension d'exploiter une carrière - Le Saint (56) - Insectes - inventaire non standardisé avril 2017. 2 records from Biological rejuvenation of iron oxides in bioturbated marine sediments. 3188 records from SILENE-FAUNE-PACA - Butterfly_conservation_2017_12_18. 16465 records from Mesures compensatoires A65 - CDC Biodiversité - Inventaires faune. 3 records from Cadre d'acquisition personnel de Collet Maeva - Jeu de données personnel de Collet Maeva. 161 records from Beeinträchtigung des Bodens als Filter und Puffer für Schadstoffe gegenüber endogäischen Regenwürmern. 5 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 134490 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 527 records from [SUIVI] 2018 - Inventaire avifaune Parc éolien de Cabalas (34) - [SUIVI] 2018 comportement avifaune parc eolien cabalas. 89 records from Taxonomy and faunistics of the genus Scrobipalpa Janse, 1951 (Lepidoptera, Gelechiidae) in southern Siberia. 14 records from Coleoptera identified from the St. Paul's Academy site, Abbey Wood, London. 28881 records from Données bibliographiques et opportunistes Odonates (GON) - Données bibliographiques et opportunistes Odonates issues du SIRF. 2736 records from BD de la plateforme partagée pour la diffusion des données naturalistes de Haute-Normandie - Mise en place d'un suivi scientifique des amphibiens pour la production d’indicateurs de biodiversité. 76 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 4 records from Occurrence of mammalia relicts at site Sainte-Eulalie. 29 records from Düne am Ulvenberg (Darmstadt). 413 records from Parc éolien de Tigny Noyelle (Alterric Ferme Eolienne Sud) - Activité Chiroptère 2019 parc éolien Tigny Noyelle (Alterric Ferme Eolienne Sud). 9 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Céline DELTORT. 1 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de VENEL Jean-Marc. 7 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes d'Emilie WEBER. 290 records from Plantation de vignes à Belle-Ile-en-Mer sur les communes de Bangor et Locmaria - Campagne faunistique TBM environnement 2019 – Vignoble Belle-Île. 26320 records from Mammals housed at MHNG, Geneva. 349 records from Grand Paris Express - Ligne 15 Est - L15E_Etat initial faune flore (2019). 18310 records from Projet de parc éolien en mer des îles d'Yeu et de Noirmoutier - demande de dérogation espèces protégées - Chauves-souris - Points d'écoute au sol. 93 records from Projet éolien de Buzançais - Inventaire Chiroptères. 21 records from Projet de centrale photovoltaïque au sol sur la commune de Beylongue (40) - Faune. 4 records from Projet de centrale photovoltaïque au sol sur la commune de Saint-Mard (17) - Reptiles. 5398 records from Löydös Open Invasive Species Observations. 116 records from Données personnelles opportunistes Orthoptères de Béatrice DUCOUT. 35 records from Grillhütte Wettsaasen, Wiese, Hecken. 2134 records from Données brute suivi environnemental 2018 - parc éolien de Touvent (80). 7 records from Autorisation 2018-14 - Station Biologique de Paimpont. 1549 records from Swiss Psyllid (Hemiptera) Collections - Basel. 155 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste VAN DEN BRINK Sylvie provenant de la base de donnée du SINP Île-de-France CETTIA. 13721 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes d'Alain CANARD. 78 records from Projet pilote d'ombrière agrivoltaïque de Brouchy - Brouchy - Insectes. 7 records from Plan de gestion 2018 - 2022 du site de Saulié (47) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Nouvelle-Aquitaine. 10 records from Plan de gestion multi-site 2018 - 2022 des étangs de Mios (33) mené par le CEN Nouvelle-Aquitaine - Observations d'oiseaux réalisées par le CEN Aquitaine selon le protocole STOC EPS. 580 records from 2017_LPO PACA_1. 14 records from Refondation - Construction d’une nouvelle imprimerie et d’un nouveau centre fiduciaire sur le site de Vic-Le-Comte à Longues - Mammifères - Inventaire non standardisé.. 9 records from Données poissons et écrevisses issues de bureaux d'études ou autres organismes - Données poissons issues du BE Bellariva. 219 records from Les os de seiches sur les plages de métropole - Données de la quête INPN Espèces : Suivi de l'invasion du Frelon asiatique.. 4 records from Validation of the status of a species with high CO 1 and low nuclear genetic divergences: the scab mite Caparinia ictonyctis stat. res. (Acariformes: Psoroptidae) parasitizing the African hedgehog Atelerix albiventris. 1634 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 2 records from 2014_Parc National de Port Cros_2. 1638 records from Ferme éolienne de l'Algoux - Avifaune. 116 records from CardObs : Observations naturalistes issues de l'outil CardObs - données bibliographiques diverses (non araignées). 975 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Merle noir 2002 - 2006 Coordonnées GPS Lambert 93. 467 records from Expertise IQE - Laimont 2018 - Données espèces - IQE Laimont 2018. 1 records from EDP Baixo Sabor: Phytoplankton - Ecological Monitoring Program [2016]. 1 records from Bird specimens of Komatsu City Museum. 159 records from Autoroute A13 - Complément du demi-diffuseur de Heudebouville vers Rouen - Oiseaux - Inventaire non standardisé.. 6 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de BRULE Hervé. 52 records from Ferme éolienne de Lion-en-Beauce - Avifaune hivernale. 2 records from Projet de parc solaire Figanieres - Mammifères - Inventaire non protocolé. 84 records from Projet éolien de Crèvecoeur le Grand (SEPE Les Haillis) - HAILLIS_faune_2014-2015. 3279 records from Macro- and megafauna from the North Aegean Sea from 1997-1998. 2 records from Boreonemoral regnskog på østsiden av Lygrespollen. 1583637 records from Données naturalistes opportunistes Faune-France - Données Naturalistes Faune-France 2020 Communes. 8 records from Projet éolien Géranium - Inventaire faune et flore projet Clais. 23 records from Données espèces - Expertise IPE - Val estuaire - 2013. 140 records from Projet de parc éolien SEPE La Blanche Côte - Données biodiversité liés au projet éolien de Vanault le Châtel - chiro au sol. 50 records from Beetles on polypores at 4 sites in Norway. 1 records from Collection Crustacea - ZSRO. 28 records from Projet monomères phase 1 - Inventaire avifaune – Egis 2016 – GPMD (Extrait pour le projet SNF). 1 records from 1ère phase d'animation (2010 - 2018) du Document d’objectifs du site Natura 2000 FR7200669 - Vallon de la Sandonie (24) menée par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 26 records from Projet éolien des Bruyères - Inventaire mammifères (hors chiroptères). 349 records from EDP Baixo Sabor: Land Birds - Reservoir Filling Phase [2015]. 724 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2007 - 2011 Coordonnées GPS Lambert 93. 1675093 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 153 records from Parc éolien de Haut Vignoble (Remaudière (la), Vallet, Regrippière (la)) - 44 - Vallet - Etude d'impacts - Avifaune. 960 records from SILENE-FAUNE-PACA - Département_du_Var_2017_12_18. 5 records from Chauvé Energies - Oiseaux - Inventaire opportuniste. 2 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 45 records from Plan de gestion 2007 - 2011 du site du Coteau de Peyroutet (47) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 48 records from Wildlife Observations Bardon Hill 31.5.09. 35 records from Projet de parc solaire Figanieres - Oiseaux - inventaire non protocolé. 7 records from Mise à 2x2 voies de la RN176 entre l'Estuaire de la Rance et l'échangeur de la Chênaie - Données_chiroptères. 91288 records from 2015_MNHN_2. 94 records from Inventaire en continu de la ZNIEFF 'Forêt du Verdus' - 720012953 - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 7 records from 2021 - Demande d'autorisation environnementale pour l'extension et le renouvellement de la carrière de la société Saviane Frères sur la commune de Beaunotte (21) de matériaux calcaires - Chiroptères inventoriés par ENCEM sur la carrière de Beaunotte en 2018. 1 records from Parc éolien de La Lys - Données faune Chiroptères mât - transit automnal. 30 records from Chaufferie CALIFORNIE - 44 REZE - Chaufferie Bouguenais - Petite Californie - Inventaire faune flore 2014-2015. 176 records from 2020_Parc Naturel Régional du Queyras_4. 63 records from Réseau Loup - Lynx ONCFS - Lynx 2009 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 783 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Annales de la Société entomologique de France [1832- ]. 13 records from Parc éolien des taillades - Suivi des chiroptères en nacelle 2021 - TAIL. 9 records from SOCPE DES QUINZE MINES - [SUIVI] Suivi post-implantation pour Quinze Mines (mortalité). 71 records from 2020_Parc Naturel Régional des Préalpes d'Azur_2. 229 records from Earthworms of mole burrows in the forest zone of Western Siberia. 1 records from Parc éolien de Vents du Catésis - Suivi de mortalité Parc éolien Vents de Catésis 2020 Eolienne CAT3. 1442 records from Projet éolien des Trois Sentiers - Avifaune. 7 records from Plan de gestion 2012 - 2016 du site des tourbières de Mées (40) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 8 records from Chaude Vallée : dépôt légal des données brutes de biodiversité 2021 - Suivi de mortalité - Chaude Vallée - 2021. 71788 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 4 records from projet centrale photovoltaïque de Trouhaut - Insectes - Inventaire non protocolé. 497 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 99 records from Programme LIFE CROAA - Eradication de la Grenouille taureau : Tir des individus. 232 records from Elaboration du DOCOB du site Natura 2000 ‘Haute Cize’ (FR7212015) - Inventaire avifaune. 132 records from Particular records of helminths from common species of herpetofauna of Ukraine. 7393074 records from iNaturalist Research-grade Observations. 2374 records from Untersuchung und Simulation der zeitlichen Dynamik von Collembolen auf verschiedenen Ackerstandorten. 5 records from The Anagyrus (Hymenoptera: Encyrtidae) parasitoids of the obscure mealybug Pseudococcus viburni (Hemiptera: Pseudococcidae) in Spain, with description of a new species. 3 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 35 records from Bohemannia auriciliella (Nepticulidae) specimen data. 64 records from Réseau Loup - Lynx ONCFS - Lynx 1996 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 33 records from Projet de parc éolien des Moulins de la Cologne - Données chiroptères au sol - Moulins de la Cologne. 3690 records from Comptage décadaires oiseaux d'eau des Espaces protégés (LPO France) - Comptage décadaires | RNN Sept-Iles. 66 records from Parc de loisirs historique Le Bois du Roy - Données Naturalistes du projet de parc de loisir historique du Bois du Roy. 923 records from Aménagement de l'autoroute A6 : création d'une troisième voie en sens 1 (Paris-Lyon) entre le PR156+600 et le PR169+200 (secteur Auxerre) - Chauves-souris - Points d'écoute au sol. 2253 records from Parc éolien de Carreau Manceau 2 (Dizy-le-Gros et Boncourt) - Donnees_brutes_Suivi_Environnemental_2019_2020_Energie_Dizy_ECOSPHERE. 1 records from Order Carnivora. 217 records from Atlas communaux de la Biodiversité du Parc Naturel Régional des Landes de Gascogne (PNRLG) - Inventaire des odonates 2014. 277 records from Parc éolien Saint Secondin, lieu dit les Brandes - Parc éolien terrestre de Saint-Secondin - Activité nacelle Chiroptères - 2018. 14 records from Parc éolien du Chemin Vert - CheminVert_Envol_Mammifère_Amphibiens_PE. 23 records from Projet de parc éolien SEPE La Blanche Côte - Données biodiversité liés au projet éolien de Vanault le Châtel - entomofaune. 137 records from PARC EOLIEN DE CHAMP BONNET - Données Chiro Actifs. 74 records from Ferme éolienne de la Queue d'Ane - Avifaune_IPA_Nicheurs. 694 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données arachnologiques de CARR David. 283 records from Eurytemora affinis in the Sluice Dock Oostende (1970-1971). 370 records from Ferme Eolienne de Maisontiers 2 - DonnéesBiodiversité_Maisontiers2_ENCIS Environnement. 1680 records from Regroupement d'études et inventaires - Collecte données faune Simethis 2014-2019. 11 records from Ferme éolienne du Mont de Trême SAS - Mont-de-Trême (80) - suivi année 1 - mortalité 2019 oiseaux chiroptères. 262 records from Ferme éolienne d'AVESSAC - Parc éolien terrestre d'Avessac - Mortalité - Chiroptères & Aves - 2019 - E03. 5406 records from Inventaire des Lépidoptères Rhopalocères et Zygènes de France métropolitaine - Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache.. 932 records from Die Nematodenfauna eines Fichtenforstes. 16 records from Parc Eolien de la Coutancière - Inventaire Amphibiens. 187 records from Feeding rhythms of the common goby Pomatoschistus microps at the brackish tidal marsh 'Het verdronken land van Saeftinge' in 1994. 185 records from 2018_Département du Var_1. 2346 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de SUBIT Patrick. 131 records from BIRDRACE Griffin Wood Warblers. 85 records from Données espèces -expertise IQE - Lesménils - 2013. 21 records from Parc éolien du Clos des Ajoncs - Projet éolien Clos des Ajoncs_chiro. 1 records from Construction d'une plateforme logistique à Montélimar - Inventaire des amphibiens pour le projet de plateforme logistique à Montélimar. 158 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de GERBAUD Joël. 169 records from Festschrift für Zschokke.. 157 records from Projet artère de l'Adour réalisé par ECOSPHERE - Inventaire et suivi Rhopalocères. 157 records from BIRDRACE Rheinische Wasserrallen. 95 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 2004. 5 records from Cadre d'acquisition personnel de Caussade Philippe - Jeu de données personnel de Caussade Philippe. 12 records from PLATEFORME LOGISITIQUE FM FRANCE ETREPILLY - Mammifères. 11 records from Mise en souterrain partielle de la ligne électrique à 63 000 volts Aussois-Terres Froides - Reptiles - Inventaire non standardisé.. 54 records from CPENR Les Galacées - Galacées chiroptères_ballon. 236 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de David HAPPE. 2267 records from Parc éolien de La Baume - La Baume : suivi d'activité avifaunistique 2017-2021. 2224 records from 2012_SMAVD_1. 99 records from 2014_Parc Naturel Régional des Baronnies_1. 1 records from Régularisation administrative du circuit de sports motorisés de Pont-de-Vaux - Relevés amphibiens. 153 records from AUNEAU 1 - Projet de plateforme logistique à Auneau (28) - Faune Flore. 5348 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données coléoptères de l'Association des Entomologistes de Picardie. 380 records from Collembola of the Chernaya river basin. 15416 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 24 records from Suivi écologique 2018 sur le canal de Miribel et de la parcelle du Rizan suite à une opération forestière (année n+2) - Chiroptères. 1 records from Données d'observation de la Faune, de la Flore et de la Fonge - [MILIEU] - Zone humide d'altitude - Inventaire. 11 records from Projet de Parc éolien de Reuilly & Diou - [COMPLEMENTS] Suivi post-implantation. 514 records from EDP Foz Tua: Bat Roosts - Ecological & Compensatory Measures Monitoring Programs [2011-2017]. 661 records from GEO Biodiversity Day. 1079 records from Biodiversity in Width and Depth (BIOWIDE). 15 records from Animation des 4 sites Natura 2000 des zones humides du Marensin - Inventaire et suivi de la Cistude d’Europe sur le site Natura 2000 ‘Zones humides de Moliets, La Prade et Moisans’ (FR7200718). 579 records from Parc Eolien de Laucourt / Beuvraignes - Ecoutes en hauteur chiro. 29 records from IASTracker. Invasive Alien Species database. 1 records from 2022_Parc National de Port Cros_2. 8 records from Réseau Loup - Lynx ONCFS - Lynx 1988 présence Régulière Mailles 10km Réseau Loup-Lynx ONCFS. 61090 records from Ornitho.eus. 22 records from Parc éolien de Quincy-le-Vicomte 1 - [SUIVI] Suivi post-implantation pour le parc éolien Quincy 1 (mortalité). 311 records from Projet de centrale photovoltaïque au sol de Bayet. 27509 records from Fishes of INEP and NFH collections. 233162 records from Terrestrial and limnic invertebrates systematic collection, NTNU University Museum. 2 records from Projet d'aménagement de parc naturel paysager du Sempin, à Chelles (77) et Montfermeil (93) - Mammifères - Inventaire non protocolé - EGIS. 19 records from E.R.L_SUIVIS ENVIRONNEMENTAUX_2021 - ERL - suivi mortalité 2021. 49 records from Naturpark Kottenforst-Ville 19.6.09. 25 records from Liaison autoroutière concédée entre Machilly et Thonon les Bains et suppression des passages à niveau N° 65 et 66 à Perrignier Haute-Savoie - Amphibiens - Inventaire non standardisé - ASTERS. 5 records from Inventaires et suivis programme Lagunes mené par le Département des Landes - Ensemble des données Mammifères. 16 records from Demande d'Autorisation Environnementale pour la création d'un datacenter sur la commune de Les Ulis (91) - Inventaire des mammifères terrestres (projet de datacenter). 935 records from 2022_Amis des Marais du Vigueirat_3. 73 records from Swedish Malaise Trap Project (SMTP) - small Sciaroidea families. 239 records from PE des Quatre Chemins - Données MNHN Quatre CheminsChiropteres - Ecoute passive. 24 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" site de La Beute (Tosse). 190 records from 2022_Communauté de Communes des Alpes d'Azur_3. 1 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 75 records from Centrale photovoltaïque au sol d'Oberhoffen. 628 records from hauterivian_echinoids_of_the_paris_basin. 51 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaires "Espaces Naturels Sensibles" du Luy (Saugnac-et-Cambran). 14 records from Réserves Naturelles de France (RNF) - RNF - Données de la Réserve Naturelle du Marais de Lavours. 18 records from Parc éolien de Coulanges - Données de mortalité - Suivi environnemental 2021 NAY. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 396 records from Inventaire général de la biodiversité du domaine du Bois de Bouis (IGB/ATBI) - Inventaire général de la biodiversité (IGB/ATBI) Domaine Bois de Bouis - Données suivi orthoptères 2017-2019. 179 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 11 records from Suivi post-implantation 2021 parc éolien IDS - [SUIVI] Suivi post-implantation 2021 pour le parc éolien d'Ids (nacelle). 39 records from BioAcoustica: Wildlife Sounds Database. 773 records from Projet d'aménagement de la Colline d'Elancourt - Inventaires colline d'Elancourt. 47 records from Etude avifaunistique de la LPO Limousin sur les landes haut-viennoises - Inventaire et suivi Avifaune de la lande de Massaloux. 1 records from Cadre d'acquisition personnel de FALLOUR Delphine - Jeu de données personnel de FALLOUR Delphine. 7 records from TransForest - vegetation, lichen and fungi data 2016. 32 records from projet centrale photovoltaïque de Selongey - Oiseaux - Inventaire non protocolé. 1643 records from Mesures compensatoires autoroutes - Données mesures compensatoires ASF - OPIE. 17768 records from Biowide Species data. 8 records from 2019_Parc National de Port Cros_9. 11 records from Elaboration du DOCOB du site Natura 2000 ‘Zones humides de Moliets, la Prade et Moïsan’ (FR7200717) - Inventaire et regroupement de données Natura 2000. 5 records from Projet d'aménagement de la ZAC Satory Ouest - Oiseaux - Inventaire non standardisé - 1. 36 records from Ferme éolienne de Massay 2 SAS - Suivi environnemental sur 4 années pour la mortalité de l'avifaune. 6 records from Parc éolien de Stenay - Suivi de la mortalité 2021 - STENAY. 18 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Vincent DUPRAT. 1 records from Parc Eolien BASSE THIERACHE NORD - Suivi mortalité BTN 2021 - Cadavre 7 éolienne BTN 4. 391 records from CardObs : Observations naturalistes issues de l'outil CardObs - Inventaire Mollusques ZAC Royon 2020. 14 records from Projet de centrale photovoltaïque au sol du Massif de l’Etoile - Insectes - Inventaire non protocolé. 201 records from Schanzenanlage Bergham. 24 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 57 records from Mise en souterrain partielle de la ligne électrique à 63 000 volts Aussois-Terres Froides - Insectes - Inventaire non standardisé.. 7 records from Contributions to the study of the grasshopper (Orthoptera: Acrididae Gomphocerinae) courtship songs from Kazakhstan and adjacent territories. 295 records from Free-living plathelminthes of marine habitats near Wimereux (1990-1991). 160 records from AVJNF: Søholt Storskov, amphibian survey. 90 records from Parc éolien d'Hannappes et Bossus-lès-Rumigny - inventaire spécifique 2018 des oiseaux nicheurs patrimoniaux. 1702 records from Données du Comité Départemental de Protection de la Nature et de l'Environnement de Loir-et-Cher (CDPNE) - CDPNE - Données publiques 2019. 835 records from Biodiversity of Zmiinyi Island. 25 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 42 records from Inventaire des oiseaux pour le projet de parc solaire de Ribeyret. 48 records from 80 - Parc éolien Maissel (Heudicourt, Liéramont, Sorel) - 80 - Liéramont - Activité chiroptères 2020. 23 records from Mesozooplankton South Adriatic-PRISMA1-Flussi Project. 285 records from Abundances and biological traits of the juveniles trout sampled in the survey of trout abundance Indices (VIGITRUITE®) in the Bresle river (France). 1 records from Parc photovoltaïque Val Varinot - REPTILES_VAL_VARINOT. 86 records from Siphonaptera and Phthiraptera Recording Scheme - records verified via iRecord. 19 records from Schulgelände SGD/Viersen. 1533 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 29 records from Parc éolien de Champcourt - Suivi mortalité Marle Champcourt 2020. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 27 records from TOPP Summary of SSM-derived Telemetry. 115 records from Réseau Loup - Lynx ONCFS - Répartition Régulière Lynx 2020. 3784 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de Ségolène FAUSTEN. 110 records from Demande d’autorisation environnementale pour le renouvellement, l’extension et l’approfondissement de la carrière « le Mont Colquin » située sur le territoire de la commune de Doville - Etude écologique - Inventaires faune-flore 2016. 1 records from Cadre d'acquisition personnel de Landré Aude - Jeu de données personnel de Landré Aude. 5056 records from MZL Invertebrate Collections. 14 records from Two New Species Of Dictyogenus Klapálek, 1904 (Plecoptera: Perlodidae) From The Jura Mountains Of France And Switzerland, And From The French Vercors And Chartreuse Massifs. 35 records from Projet Refondation à Vic le Comte - Mollusques - Inventaire non standardisé. 365 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 38 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 13758 records from Collection of Coleoptera. 345 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données arachnologiques de LEUCHTMANN Maxime. 1707 records from Eoliennes vent de seine - Parc éolien de Seine Rive Nord - Données brutes 2021 post-implantation parc éolien SRN - Acoustique Chiro P2. 1215 records from 2014_Ecosphère_1. 280 records from GEMFI CRIQUEBEUF - Insectes - Inventaire non protocolé. 1 records from ICPE - Suivi environnemental 2019 du parc éolien "Le Grand Champ" - Biotope_OISEAU_INV_suivi_icpe_2019_GC. 837 records from Inventaires et suivis programme Lagunes mené par le Département des Landes - Ensemble des données Rhopalocères. 738 records from Projet éolien de Buzançais - Inventaire Avifaune. 150 records from 2022_LPO PACA_11. 1392 records from Projet de Régénération sur la ligne 42000 Lure Aivillers - Travaux 2021, 2022 et 2023 - L42000_Lure Aivillers_REGE 2021 2022 2023_Inventaire faune flore 2021. 5 records from The InBIO Barcoding Initiative Database: DNA Barcoding reveals sexual dimorphism in Isotrias penedana Trematerra, 2013 (Lepidoptera: Tortricidae, Chlidanotinae). 8 records from Parc éolien de Haut de Vausse - 2021 - Suivi de mortalité parc éolien Haut de Vausse - 2021. 3045 records from Parc éolien la Croix de la Mérotte - Données Biodiversité Etude d'impact parc éolien Croix de la Mérotte. 45 records from Plan de gestion 2015 - 2019 du site du Coteau de Monco (33) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 1990 records from Parc éolien du Plateau de La Perche - Chauves-souris - Points d'écoute au sol. 136 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Inventaire faunistique de l'ENS des Parc des berges de Seine. 11 records from Plateforme de transit de déblais d'Aulnay-sous-Bois - Etat initial faune. 4881 records from Soil invertebrates occurrences in European North-East of Russia. 568 records from Queensland Museum provider for OZCAM. 505 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de MATIGNON Théo. 156 records from Eoliennes de Nieul-le-Dolent - Projet éolien de Nieul le Dolent - Etat initial. 39 records from Inventaire en continu de la ZNIEFF 'Pechs De Bouyssou Et De Vitrac' - 720020098 - Pechs de Bouyssou et de Vitrac - Inventaires Oiseaux IPA. 165 records from Les éoliennes de Conquereuil - Parc éolien terrestre de Conquereuil - Mortalité - 2021 - E3. 32 records from PIROP Northwest Atlantic 1965-1992. 18 records from Ferme éolienne de Monterfil - Mammifères terrestres - Inventaire non protocolé. 93 records from 2022_NATURALIA_5. 91 records from Mutualisation des données naturalistes pour le rapportage Natura2000 en 2017 - Synthèse 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recensée de 2013 à 2017. 4673 records from Projet éolien des Portes du Porcien - chiro hauteur. 125 records from Plan de gestion 2013 - 2018 du Lac de La Prade (33) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1009 records from UWFC Ichthyology Collection. 84 records from Etude d'aménagement foncier lié à la desserte du CHNDS - Inventaire de Lépidoptères et des Odonates. 12 records from Parc éolien de la Grande Combe - Suivi de mortalité - Grande Combe - 2021. 779 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle des bois 1996 - 2000 Coordonnées GPS Lambert 93. 68 records from Auburn University Museum of Natural History Invertebrates. 3575 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18. 3 records from Rhamphomyia Meigen of the Canadian Arctic Archipelago, Greenland and Iceland (Diptera: Empididae). 74 records from Animation du site Natura 2000 ‘La Vallée de l'Avance’ (FR7200739) - Données opportunistes. 50 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes opportunistes de Cedric DEVILLEGER. 34 records from Parc éolien d'Orvilliers Saint Julien - Suivi avifaune 2019 parc éolien Orvilliers. 1213 records from Mammals in Tawny Owl (Strix aluco) pellets from Kharkiv Region, Ukraine. 38 records from Projet Photovoltaïque Flottant Partie A Cahuzac sur Adour - Station faune. 3 records from 26 VALENCE-ST MARCEL LES VALENCE DREAL RN7- Aménagement du carrefour des Couleures - Insectes patrimoniaux - Inventaire non standardisé. 182 records from Centrale Photovoltaïque de la Baconnière - Données brutes de biodiversité Centrale PV de la Baconnière (49450). 108 records from Réseau Loup - Lynx ONCFS - Lynx 2015 présence Occasionnelle Mailles_10km_LAEA Réseau Loup-Lynx ONCFS. 126 records from CUMV Fish Collection. 4 records from New Oligaphorura species (Collembola: Onychiuridae) from the forests of East Asia. 6816 records from MUST, Insecta. 24 records from Suivi et déplacement d'amphibiens pour la construction de la liaison RD656/RD119 et des carrefours associés (Amorce de la rocade Ouest d'Agen) - Déplacement d'amphibiens dans le cadre du chantier. 751788 records from Données ONF faune-flore-fonge. 13 records from Observations occasionnelles de taxons par les agents de la Fédération (hors inventaires scientifiques) - Inventaire opportunistes Faune. 901 records from Ferme Éolienne de Saint Maurice - 79 - St Maurice Etusson - Chiroptères - Mât de mesure. 1963 records from Données Ligue de protection des oiseaux de Touraine - LPO Touraine - Données oiseaux 2019. 13 records from Deutsche Schule Budapest. 1463 records from Regroupement d'études et d'inventaires - Regroupement de données rhopalocères récoltées sur la période de 2010-2015 par Cistude Nature. 1 records from Occurrence of mammalia relicts at site Trebacki krs. 42 records from Notice de gestion 2019 - 2023 de la bande de servitude de l'artère Girland (40) de Teréga mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1394 records from Ferme éolienne de Mauprévoir - Données Mauprévoir - oiseaux. 594 records from Demande d'autorisation de renouvellement et d'extension de la sablière "la Saulaie" à JUVARDEIL (49) - Données LPO Anjou. 4862 records from Données biodiversité Projet éolien d'Ormesnil (76). 2324 records from University of Michigan Museum of Zoology, Division of Mollusks. 2 records from Weevils (Curculionoidea) from the UWIZM Land Arthropod collection. 12 records from Projet éolien de la Montie - Chiroptères étude mât 10m automne. 25 records from Projet éolien des Trois Sentiers - Chiroptères - écoutes passives. 67 records from Données acquises par le Conservatoire botanique national du Bassin parisien et son réseau (bénévoles, associations, autres structures professionnelles) - Données acquises via le réseau du Conservatoire botanique national du Bassin parisien. 12 records from JONCELS ENERGIE_SUIVIS ENVIRONNEMENTAUX_2018-2019 - JONCELS ENERGIE - suivi chiroptères 2019. 1436 records from Inventaires et suivis sites compensation contournement sur la commune de DAX - Données opportunistes. 388 records from Projet de parc éolien du Balinot - Données biodiversité - parc éolien du Balinot. 2253 records from DASSH Data Archive Centre Academic Surveys. 2 records from A new species of Streblospio (Polychaeta: Spionidae) from the northern Adriatic Sea (Mediterranean Sea). 4 records from Projet éolien de La Couture Energies - Suivi busards 2021. 40 records from Occurrence of mammalia relicts at site Roc de Combe. 246 records from Mont-de-Transet E3 - Données naturalistes - Etude d'impact. 245 records from Suivi de travaux : Vannes de l’Estrabeau (Engranne) Moulin des 4 ponts (Gestas) - Inventaire macroinvertébrés. 44 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 12 records from PARC EOLIEN DE DAMMARIE - Données brutes mortalités Dammarie. 1 records from Inventaires et suivis sites compensation village ALZHEIMER sur la commune de DAX - Ensemble des données. 21 records from Exkursion Ebertsheimer/Grünstädter Berg. 5763 records from University of Florida Invertebrate Paleontology. 9 records from Opération d'aménagement de la ZAC Garonne Eiffel, Quartier SOUYS (33) - Chiroptères - Inventaire non standardisé. 62 records from Observations naturalistes de la réserve naturelle nationale des prés salés d'Arès et de Lège-Cap Ferret - Plan de gestion 2016-2020 - Inventaire et suivi Faune - Protocole Wetlands International. 8 records from Rissoidae gastropods of the outer continental shelf and slope off Galicia (NW Spain). 6 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de Thibault RAMAGE. 122 records from Centrale au sol_Puy Long - Données biodiversité_Puy Long. 43 records from Vogelstimmenführung durch den Tiergarten. 1477 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Bulletin de la Société Linnéenne de Bordeaux. 2896 records from Localizaciones satélite de un ejemplar ("Lorien") de águila azor perdicera (Aquila fasciata Vieillot, 1822) en Aragón. 16735 records from Enquêtes de l'Opie - Inventaire des Ephémères de métropole (Opie). 49 records from Echinodermata of Montenegro (South Adriatic). 124 records from Réseau Loup - Lynx ONCFS - Lynx 2007 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 44 records from Database of Arctic lamprey (Lethenteron camtschaticum (Tilesius, 1811)) occurrences in Russia and actual samples deposited in the A.N. Severtsov Institute of Ecology and Evolution.. 177 records from DECLARATION DE PROJET EMPORTANT LA MISE EN COMPATIBILITE DU PLUm POUR LA CONSTRUCTION DU COLLEGE DE LEVENS - Oiseaux - Inventaire non protocolé. 246 records from ZMAA Aves collections of Åbo Akademi. 195 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Giordano Charlotte provenant de la base de donnée du SINP Île-de-France CETTIA. 6497 records from Phenology and biological traits of adult migrating atlantic salmon (Salmo salar) sampled by trapping in the survey in the Nivelle river (France). 22 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Propriété régionale du Moulin des Marais - Inventaire naturaliste 2015. 14 records from University of Kentucky Insect Collection. 15 records from Autoroute A6 : création d'un demi-diffuseur au nord de Chalon-sur-Saône - Amphibiens - Inventaire non standardisé.. 49863 records from Atlas des Orthoptères et Mantides de France métropolitaine. 64 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Bourdin Dominique provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from Parc éolien de Fécamp - Suivi mortalité ICPE 2015 - Fécamp. 94 records from UAM Bird Collection (Arctos). 21 records from Twite, winter distribution in Caithness and Sutherland 2006/7. 85 records from Projet d'extension de la carrière de Le Blanc, Queyrac - Données brutes de biodiversité - Le Blanc, Queyrac. 1 records from Description of Metarhabditis giennensis sp. n. (Nematoda, Rhabditida, Rhabditidae) from decaying wood of a riverbank forest in the southern Iberian Peninsula. 643 records from ZFMK Crustacea collection. 391 records from SILENE-FAUNE-PACA - GEOECOLINK_2017_12_18. 2 records from Updates to the bee fauna of Portugal with the description of three new Iberian Andrena species (Hymenoptera: Apoidea: Anthophila). 9 records from 2022_KLM Environnement_1. 154555 records from The Scottish Squirrel Database. 158 records from Centrale Photovoltaïque de Donzère Sud - Parc PV Donzère avifaune suivi 2021. 2045 records from Carrière calcaire de Chateaupanne (Mauges-sur-Loire) - modification des conditions d'exploitation - renouvellement de l’autorisation - inventaires 2004-2014 pour étude d'impact carrière. 96 records from BIRDRACE OAG Neuwerk. 51 records from Pittosporum sucker (Trioza vitreoradiata) records aquired by the Royal Horticultural Society. 36 records from Selz (Ingelheim am Rhein). 2 records from Accidental monstrosities: Taxonomic chimeras in Ostracoda (Crustacea). 119 records from Expertise batrachologique de la lande de Puycheny la Rouseille par le GMHL en 2013 - Inventaire des données batrachologique. 3410 records from Continuité d'exploitation de l'installation de traitement et de stockage de déchets dangereux de Graulhet - Etudes écologiques du projet de continuité d’exploitation de l’ITSDD OCCITANIS. 1 records from Cadre d'acquisition personnel de Debise Grégoire - Jeu de données personnel de Debise Grégoire. 29 records from pins. 217 records from Survey dataset on Pomatoschistus minutus (Pallas, 1770) and other gobies at the Belgian Coast, Oosterschelde, Westerschelde and at nuclear plants near Doel & Borssele. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 48 records from Projet éolien Doubs-Ouest 2 - INV_AVIFAUNE_NICHEUSE_2015. 401 records from SMNG_Myriapoda_Ansorge. 181 records from [SUIVI] - 2021 Inventaire annuel Parc éolien Grand Gats (44) - [SUIVI] Ecoute chiroptère et suivi avifaune 2021 Grand gats. 205 records from 2020_GCP_3. 1 records from Suivi Environnemental 2021-2022 Ferme éolienne des Tilleuls - Mortalité éolienne T03 25/08/2021 Tilleuls. 6126 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes de Monsieur LAFAGE Denis. 98 records from Dossier de demande d'autorisation environnementale pour l'exploitation d'une sablière pour partie sous eau - Inventaires Faune-Flore. 989 records from IPAE egg clutches collection (Aves). 1 records from Molche in Ruschwedel. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 9115 records from Données orthoptères en Auvergne, observations d'Emmanuel Boitier. - Données d'observations d'orthoptères en Auvergne, d'Emmanuel Boitier, de 1998 à 2015.. 1128 records from Atlas de la Biodiversité Communale (ABC) de la Communauté de Communes de la Vallée de l'Homme (24)-Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 119 records from Rénovation du réseau électrique de la Haute Vallée de l'Aude - projet Usson Gesse Nentilla - Reptiles - Inventaire non standardisé. 16 records from Parc éolien de La Plane ou dit de Salles Curan - Suivi mortalité ICPE 2018-2019. 965 records from 07-Boralexforetdebauzon - Projet éolien de la Forêt de Bauzon études avifaune et faune 2016/2017. 158 records from Herpetofauna and other animals registered within Rzhyshchiv city amalgamated territorieal community (CATC) (Kyiv region) in 2021. 18 records from Parc PV flottant de Chateauneuf-du-Rhône - le Balafray - PV Flottant Chateauneuf du Rhône Le Balafray Données mammifères 2018 2019. 16 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 2 records from Plan de gestion 2015 - 2020 du site du site des zones humides du Mondarrain et de l'Artzamendi (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 1579 records from ACR BioarchéoDat - Inventaires archéozoologiques et archéobotaniques de France. 727 records from CardObs : Observations naturalistes issues de l'outil CardObs - Données naturalistes d'Arnaud LE NEVÉ. 22 records from Parc éolien de Champ-Feuillant - Données Busard 2020-2021. 8 records from Ferme éolienne des Buissons SAS - Données suivi mortalité par Auddicé de la Ferme éolienne des Buissons 2019. 101 records from Suivi environnemental d'exploitation du parc éolien Les Renardières SAS - Parc éolien des Renardières (10) - suivi Faucon crécerelle 2021. 1 records from Mise à jour Zones naturelles d'intérêt écologique, faunistique et floristique (ZNIEFF) - Données CEN M-P ZNIEFF. 12 records from Projet Agri-voltaïque "Chez Mesnier" - Chiropchassiecq. 15 records from PARC EOLIEN DE LA BRUYERE_SUIVIS ENVIRONNEMENTAUX_2020 - PARC EOLIEN DE LA BRUYERE - Suivis 2020 - Mortalité. 52 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 67 records from Projet de renouvellement de la carrière de Rolampont (52) - Inventaire Faune-Flore Rolampont. 30 records from Regroupement d'études et inventaires - Suivi gravières GSM. 74 records from Steinbruch Mainz-Weisenau, 3. Jahr. 50 records from Parc Eol
Keywords: GBIF; biodiversity; species occurrences